Multilayer carbon nanotube assembly, multilayer carbon nanotube dispersion, conductive material, electrode, secondary battery, planar assembly, filter, electromagnetic wave-shielding and pellicle for extreme-ultraviolet light

A multi-walled carbon nanotube aggregate with optimized particle size and scattering profiles addresses the conductivity limitations of conventional MWCNTs, enhancing electrode and battery performance and enabling applications in filters and shields.

JP2025010478APending Publication Date: 2025-01-21SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024057342
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-07
Filing Date
2024-03-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Conventional multi-walled carbon nanotubes (MWCNTs) used as electrode materials for power storage devices have limitations in enhancing conductivity, necessitating improvements to improve the performance of such devices.

Method used

The development of a multi-walled carbon nanotube aggregate with specific particle size distributions and scattering profiles, achieved through controlled synthesis and dispersion methods, resulting in high electrical conductivity.

Benefits of technology

The enhanced conductivity of the MWCNT aggregate leads to improved performance of electrodes and secondary batteries, as well as applications in filters, electromagnetic shields, and extreme ultraviolet ray pellicles, with increased stability and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010478000004
    Figure 2025010478000004
  • Figure 2025010478000005
    Figure 2025010478000005
  • Figure 2025010478000006
    Figure 2025010478000006
Patent Text Reader

Abstract

To provide a multilayer carbon nanotube assembly having high conductivity, a multilayer carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SOLUTION: A multilayer carbon nanotube has a median size of 80 nm or more in a volume-based particle size distribution obtained by a centrifugal sedimentation method when made into an aqueous dispersion of 0.004 mass% concentration, and a permeability change rate of 0.3% / hr or less measured by the centrifugal sedimentation method when made into an aqueous dispersion of 0.2 mass% concentration. The multilayer carbon nanotube is included in a multilayer carbon nanotube assembly. There are also provided a multilayer carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar assembly, a filter, an electromagnetic wave-shielding and a pellicle for extreme-ultraviolet light.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a multi-walled carbon nanotube aggregate, a multi-walled carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, a planar aggregate, a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet rays. [Background technology]

[0002] Carbon nanotubes (also called "CNTs") are substances with a cylindrical structure formed by rolling up graphene sheets in which carbon atoms are arranged in a hexagonal honeycomb pattern. CNTs have excellent properties such as electrical conductivity, thermal conductivity, and heat resistance, and are therefore expected to be used in a variety of electronic materials, including as electrode materials for power storage devices. CNTs are basically broadly classified into single-walled carbon nanotubes (also called "SWCNTs") formed from a single layer of graphene sheets, and multi-walled carbon nanotubes (also called "MWCNTs") formed from multiple layers of graphene sheets. MWCNTs have the advantage of being more thermally and chemically stable than SWCNTs, and in recent years, attempts have been made to more effectively improve the properties of MWCNTs.

[0003] For example, Patent Document 1 discloses MWCNTs that are CNTs having two or more coaxial layers of graphene sheet cylinders in which carbon atoms are arranged in a hexagonal honeycomb pattern, with the diameter of the outermost layer being 3 nm to 15 nm based on observation of an image using a transmission electron microscope, and the length being 1.0 mm or more based on observation of an image using a scanning electron microscope. The MWCNTs described in Patent Document 1 are said to have improved applicability to materials that require high electrical conductivity, high thermal conductivity, and the like. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-180028 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, interest in the usefulness of MWCNTs as electronic materials has been growing. For example, when MWCNTs are used as an electrode material such as a conductive additive, they can impart high conductivity to the electrodes, which is expected to improve the performance of electricity storage devices. However, conventional MWCNTs, including the MWCNTs described in Patent Document 1, still have room for improvement in terms of the effect of improving electrical conductivity when used as an electrode material in an electrode.

[0006] The present disclosure has been made in consideration of the above circumstances. An object of one embodiment of the present disclosure is to provide an aggregate of multi-walled carbon nanotubes having high electrical conductivity. Another problem to be solved by another embodiment of the present disclosure is to provide a multi-walled carbon nanotube dispersion, a conductive material, an electrode, a secondary battery, and a planar assembly, each of which includes the multi-walled carbon nanotube aggregate. Another problem to be solved by another embodiment of the present disclosure is to provide a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet rays using the above-mentioned planar assembly. [Means for solving the problem]

[0007] Specific means for solving the above problems include the following aspects. [1] An aggregate of multi-walled carbon nanotubes, comprising multi-walled carbon nanotubes that, when dispersed in water at a concentration of 0.004% by mass, have a median diameter of 80 nm or more in a volume-based particle size distribution obtained by centrifugal sedimentation, and, when dispersed in water at a concentration of 0.2% by mass, have a rate of change in transmittance measured by centrifugal sedimentation of 0.3% / hour or less. [2] When dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q = 0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S1 / S2 of 90 or more, the ratio being the scattering intensity S1 / S2 in the multi-walled carbon nanotube. [3] When dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q = 0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being the scattering intensity S3 / S4 in the multi-walled carbon nanotube array relative to the scattering intensity S4 in the multi-walled carbon nanotube array. [4] When the powder is dispersed in water at a concentration of 0.004% by mass, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more; when the powder is dispersed in water at a concentration of 0.2% by mass, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less; and when the powder is dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q = 0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S1 / S2 of 90 or more, the ratio being the scattering intensity S1 / S2 in the multi-walled carbon nanotube. [5] When the powder is dispersed in water at a concentration of 0.004% by mass, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more; when the powder is dispersed in water at a concentration of 0.2% by mass, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less; and when the powder is dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q = 0.02 nm. -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being the scattering intensity S3 / S4 in the multi-walled carbon nanotube array relative to the scattering intensity S4 in the multi-walled carbon nanotube array. [6] When dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q = 0.2 nm -1Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The scattering intensity ratio S1 / S2, which is the ratio of the scattering intensity S1 to the scattering intensity S2 in the scattering profile, is 90 or more, and the magnitude q of the scattering vector in the scattering profile is 0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being the scattering intensity S3 / S4 in the multi-walled carbon nanotube array relative to the scattering intensity S4 in the multi-walled carbon nanotube array. [7] The aggregate of multi-walled carbon nanotubes according to any one of [1] to [6], wherein the multi-walled carbon nanotubes have a maximum length of 1000 μm to 30000 μm. [8] The aggregate of multi-walled carbon nanotubes according to any one of [1] to [7], which is a conductive assistant. [9] A multi-walled carbon nanotube dispersion liquid comprising the aggregate of multi-walled carbon nanotubes according to any one of [1] to [7] and a dispersion medium.

[10] A conductive material comprising the aggregate of multi-walled carbon nanotubes according to any one of [1] to [7].

[11] An electrode comprising an electrode active material and the conductive material according to

[10] .

[12] A secondary battery comprising the electrode according to

[11] .

[13] A planar aggregate comprising the multi-walled carbon nanotube aggregate according to any one of [1] to [7].

[14] A filter using the planar assembly described in

[13] .

[15] An electromagnetic wave shield using the planar assembly described in

[13] .

[16] A pellicle for extreme ultraviolet radiation using the planar assembly described in

[13] . Effect of the Invention

[0008] According to one embodiment of the present disclosure, a multi-walled carbon nanotube aggregate having high electrical conductivity is provided. According to another embodiment of the present disclosure, there are provided a multi-walled carbon nanotube dispersion, an electrode, a secondary battery, a conductive material, and a planar assembly, each of which includes the multi-walled carbon nanotube aggregate. According to another embodiment of the present disclosure, there is provided a filter, an electromagnetic wave shield, and a pellicle for extreme ultraviolet rays, which use the above-mentioned planar assembly. [Brief description of the drawings]

[0009] [Figure 1A] 1 is a scanning electron microscope (SEM) photograph of a dispersion liquid containing MWCNT aggregates in Example 1. [Figure 1B] 1 is a scanning electron microscope (SEM) photograph of a dispersion liquid containing SWCNT aggregates in Comparative Example 1. [Figure 1C] 1 is a scanning electron microscope (SEM) photograph of a dispersion liquid containing MWCNT aggregates in Comparative Example 2. [Diagram 2] 1 is a graph showing scattering profiles obtained by a small-angle X-ray scattering method for the MWCNT aggregate of Example 1, the SWCNT aggregate of Comparative Example 1, and the MWCNT aggregate of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the multi-walled carbon nanotube aggregate, multi-walled carbon nanotube dispersion, conductive material, electrode, secondary battery, planar aggregate, filter, electromagnetic wave shield, and pellicle for extreme ultraviolet rays according to the present disclosure will be described in detail. The explanation of the requirements described below may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be implemented by making appropriate modifications within the scope of the purpose of the present disclosure.

[0011] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values ​​before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment.

[0013] In the present disclosure, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, so long as the intended purpose of the process is achieved.

[0014] In this disclosure, the term "fiber" is used to refer to a structure having one dimension greater than the other two. The fibers may be thread-like fibers having a circular cross section, ribbon-like fibers having a rectangular cross section, hollow, or have other shapes. From the viewpoint of increasing the electrical conductivity of the assembly of the present disclosure, the cross section of the MWCNT is preferably circular, and is more preferably hollow.

[0015] In this disclosure, "carbon nanotubes" are also referred to as "CNTs", "single-walled carbon nanotubes" are also referred to as "SWCNTs", "multi-walled carbon nanotubes" are also referred to as "MWCNTs", "multi-walled carbon nanotube aggregates" are also referred to as "MWCNT aggregates", and "multi-walled carbon nanotube dispersions" are also referred to as "MWCNT dispersions".

[0016] [Multi-walled carbon nanotube aggregates] One embodiment of the multi-walled carbon nanotube aggregate according to the present disclosure is an aggregate of multi-walled carbon nanotubes, comprising multi-walled carbon nanotubes having a median diameter of 80 nm or more in a volume-based particle size distribution obtained by centrifugal sedimentation when dispersed in water at a concentration of 0.004% by mass, and having a rate of change in transmittance measured by centrifugal sedimentation of 0.3% / hour or less when dispersed in water at a concentration of 0.2% by mass. In the present disclosure, the multi-walled carbon nanotube aggregate according to this embodiment is also referred to as "MWCNT aggregate (A)".

[0017] The MWCNT aggregate (A) according to the present disclosure has high electrical conductivity. The reason why the MWCNT aggregate (A) according to the present disclosure has high electrical conductivity is not clear, but the present inventors speculate as follows. However, the following speculation is not intended to limit the interpretation of the MWCNT aggregate (A) according to the present disclosure, but is provided as an example.

[0018] The present inventors have obtained knowledge regarding the relationship between the median diameter in the volumetric particle size distribution obtained by centrifugal sedimentation when MWCNTs are dispersed in water at a specific concentration, and the structure formed by entanglement of MWCNTs. In particular, it has been found that a large median diameter suggests that the structure formed by entanglement of MWCNTs is large in size. The present inventors have also obtained knowledge regarding the relationship between the rate of change in transmittance measured by centrifugal sedimentation when MWCNTs are dispersed in water at a specific concentration, and the stability of the structure formed by entanglement of MWCNTs in the water dispersion. In particular, it has been found that a slow rate of change in transmittance suggests that the structure formed by entanglement of MWCNTs can stably exist in the water dispersion. In the MWCNT aggregate (A) according to the present disclosure, MWCNTs are thought to be entangled with each other to form a gigantic network structure that can exist stably in an aqueous dispersion. It is presumed that the formation of a network structure by MWCNTs results in multiple contacts between MWCNTs, forming gigantic conductive paths, thereby increasing the electrical conductivity.

[0019] In another embodiment of the multi-walled carbon nanotube aggregate according to the present disclosure, when the aggregate is dispersed in water at a concentration of 0.2 mass %, the magnitude of the scattering vector of the scattering profile obtained by a small angle X-ray scattering (SAXS) method is q=0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S1 / S2 of 90 or more, the ratio being the scattering intensity S1 / S2 in the multi-walled carbon nanotube array. In the present disclosure, the multi-walled carbon nanotube aggregate according to this embodiment is also referred to as "MWCNT aggregate (B)".

[0020] The MWCNT aggregate (B) according to the present disclosure has high electrical conductivity. The reason why the MWCNT aggregate (B) according to the present disclosure has high electrical conductivity is not clear, but the present inventors speculate as follows. However, the following speculation is not intended to limit the interpretation of the MWCNT aggregate (B) according to the present disclosure, but is provided as an example.

[0021] The present inventors have determined that the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering when MWCNT is dispersed in water at a specific concentration is q=0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 They obtained information on the relationship between the scattering intensity ratio S1 / S2, which is the ratio of the scattering intensity S1 to the scattering intensity S2 at the sample, and the size of the MWCNT primary aggregates. In detail, they found that a large scattering intensity ratio S1 / S2 suggests that the variation in the diameter of the MWCNTs is small, and that when the variation in the diameter of the MWCNTs is small, the interaction force between the MWCNTs is large, making it easier for the MWCNTs to entangle with each other and form a network structure. The MWCNT aggregate (B) according to the present disclosure has a small variation in diameter of MWCNTs, and is considered to form a network structure in which MWCNTs are entangled with each other. It is presumed that the formation of a network structure by MWCNTs results in multiple contacts between MWCNTs, forming a huge conductive path, which increases the conductivity.

[0022] In another embodiment of the multi-walled carbon nanotube aggregate according to the present disclosure, when the aggregate is dispersed in water at a concentration of 0.2 mass %, the magnitude of the scattering vector of the scattering profile obtained by the small angle X-ray scattering method is q=0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, which is the ratio of the scattering intensity S3 to the scattering intensity S4 in the multi-walled carbon nanotube array. In the present disclosure, the multi-walled carbon nanotube aggregate according to this embodiment is also referred to as "MWCNT aggregate (C)".

[0023] The MWCNT aggregate (C) according to the present disclosure has high electrical conductivity. The reason why the MWCNT aggregate (C) according to the present disclosure has high electrical conductivity is not clear, but the present inventors speculate as follows. However, the following speculation is not intended to limit the interpretation of the MWCNT aggregate (C) according to the present disclosure, but is provided as an example.

[0024] The present inventors have determined that the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering when MWCNT is dispersed in water at a specific concentration is q=0.02 nm. -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 They have gained knowledge about the relationship between the scattering intensity ratio S3 / S4, which is the ratio of the scattering intensity S3 at the sample to the scattering intensity S4 at the sample, and the entanglement of MWCNTs. In detail, they found that a small scattering intensity ratio S3 / S4 suggests that the size of the primary aggregates of MWCNTs is small, and that if the size of the primary aggregates of MWCNTs is small, the surface area of ​​MWCNTs increases, making it easier for MWCNTs to entangle with each other and form a network structure. It is believed that the MWCNT aggregate (C) according to the present disclosure has a small size of the primary aggregates of MWCNTs, and forms a network structure in which the MWCNTs are entangled with each other. It is presumed that the formation of a network structure by the MWCNTs results in multiple contacts between the MWCNTs, forming a huge conductive path, which increases the conductivity.

[0025] In the MWCNT aggregate according to the present disclosure, it can be confirmed by SEM observation that the MWCNTs are in an entangled state.

[0026] The MWCNT aggregate according to the present disclosure has high electrical conductivity and is suitable, for example, as a conductive assistant. In addition, since the MWCNTs in the MWCNT aggregate according to the present disclosure are in a state in which they are entangled with each other, they tend not to swell even when they come into contact with an organic solvent. Therefore, when the MWCNT according to the present disclosure is used as a conductive assistant when forming an electrode for a secondary battery such as a lithium ion battery, the structure is not likely to change even when the battery is operated, and the durability of the battery can be improved.

[0027] Below, the MWCNT aggregate (A) according to the present disclosure, the MWCNT aggregate (B) according to the present disclosure, and the MWCNT aggregate (C) according to the present disclosure will be described, and then other possible aspects of the MWCNT aggregate according to the present disclosure will be described.

[0028] [MWCNT aggregate (A)] The MWCNT aggregate (A) according to the present disclosure contains MWCNTs which, when dispersed in water at a concentration of 0.004% by mass, have a median diameter of 80 nm or more in a volume-based particle size distribution obtained by centrifugal sedimentation, and which, when dispersed in water at a concentration of 0.2% by mass, have a rate of change in transmittance measured by centrifugal sedimentation of 0.3% / hour or less.

[0029] The MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure preferably have a fibrous shape, from the viewpoint of facilitating the formation of a network structure through entanglement of the MWCNTs with each other.

[0030] The maximum length of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is not particularly limited, but is, for example, preferably 500 μm to 30,000 μm, more preferably 1,000 μm to 25,000 μm, even more preferably 1,100 μm to 20,000 μm, particularly preferably 1,200 μm to 18,000 μm, and especially preferably 1,300 μm to 15,000 μm. When the maximum length of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is 500 μm or more, the electrical conductivity of the MWCNT aggregate (A) tends to be higher. This is thought to be because the MWCNTs contained in the MWCNT aggregate (A) are more likely to come into contact with each other, making it easier to form a conductive path. The MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure tend to be easier to produce when the maximum length is 30000 μm or less.

[0031] In this disclosure, the length of MWCNTs can be measured by focusing on one MWCNT and taking multiple SEM photographs at adjacent viewing angles. Here, "MWCNT length" refers to the measured length of the MWCNT in the longitudinal direction, and the maximum value of the measured lengths is taken as the "maximum length." For example, when an SEM photograph of an MWCNT aggregate is taken, if one or more MWCNTs with a maximum length in the range of 500 μm to 30,000 μm are observed within the viewing angle of the SEM photograph, it is determined that the observed MWCNT aggregate contains MWCNTs with a maximum length of 500 μm to 30,000 μm.

[0032] The length of the fibrous MWCNT can be controlled, for example, by the winding capacity of the spindle used in producing the fibrous MWCNT.

[0033] The MWCNT aggregate (A) according to the present disclosure preferably contains one or more MWCNTs having a maximum length of 500 μm to 30,000 μm, and more preferably contains a plurality of MWCNTs. In the present disclosure, "MWCNT having a maximum length of 500 μm to 30,000 μm" is also referred to as "SLMWCNT."

[0034] The proportion of SLMWCNTs in the MWCNT aggregate (A) according to the present disclosure is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more, based on the number of pieces. When the ratio of SLMWCNTs in the MWCNT aggregate (A) according to the present disclosure is 10% or more on a number basis, the stability of the MWCNT aggregate (A) in an aqueous dispersion due to entanglement of the MWCNTs tends to be further improved.

[0035] In the present disclosure, the proportion of SLMWCNTs in an MWCNT aggregate is determined by taking multiple SEM photographs at adjacent viewing angles, focusing on 100 MWCNTs included in the viewing angle of the SEM photographs, measuring the maximum length of each, and identifying, among the observed MWCNTs, MWCNTs whose maximum length is in the range of 500 μm to 30,000 μm (i.e., SLMWCNTs). The same applies to the ratio of ULMWCNTs in the MWCNT aggregate and the ratio of specific ULMWCNTs in the MWCNT aggregate, which will be described later.

[0036] The diameter of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is not particularly limited, but is, for example, preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, even more preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0037] In the present disclosure, the diameter of MWCNT can be measured by taking SEM or transmission electron microscope (TEM) photographs. Here, the diameter refers to the length in the direction perpendicular to the longitudinal direction of the MWCNT, and the diameter is measured at 10 different points on one MWCNT, and the average value is taken as the diameter of the MWCNT.

[0038] The ratio of length to diameter (so-called aspect ratio) of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is preferably 1000 or more, more preferably 3000 or more, further preferably 5000 or more, and particularly preferably 10000 or more.

[0039] In the present disclosure, the aspect ratio of MWCNT can be calculated from the ratio of the maximum length to the diameter of one MWCNT. From the viewpoint of measurement accuracy, it is preferable to use the average value of the measured values ​​of 20 or more MWCNTs.

[0040] The specific gravity of the MWCNT aggregate (A) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, it is preferably 1.5 to 2.5, more preferably 1.7 to 2.4, and even more preferably 1.8 to 2.2.

[0041] In the present disclosure, the specific gravity of the MWCNT aggregate (A) can be measured by the method described in JIS Z8807:2012 "Method of measurement of density and specific gravity of solids."

[0042] The MWCNT aggregate (A) according to the present disclosure contains MWCNTs having a median diameter of 80 nm or more in a volume-based particle size distribution obtained by centrifugal sedimentation when made into an aqueous dispersion with a concentration of 0.004 mass %. When the median diameter of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is 80 nm or more, the electrical conductivity of the MWCNT aggregate (A) can be improved. The above median diameter of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is preferably 90 nm or more, more preferably 100 nm or more, and further preferably 150 nm or more. The upper limit of the median diameter of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, for example, it is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 500 nm or less.

[0043] In the present disclosure, the median diameter in the volumetric particle size distribution obtained by centrifugal sedimentation when MWCNT is dispersed in water at a concentration of 0.004% by mass is determined by the following method. Note that in the present disclosure, the "median diameter in the volumetric particle size distribution obtained by centrifugal sedimentation" refers to the particle diameter at which the cumulative frequency is 50% (so-called d50) in the volumetric particle size distribution obtained by centrifugal sedimentation. MWCNT and a dispersant are added to ion-exchanged water, and then a dispersion process is performed to obtain an aqueous dispersion of MWCNT. The amount of MWCNT added is such that the concentration of MWCNT in the aqueous dispersion is 0.004 mass%. The obtained aqueous dispersion is used as a measurement sample, and a centrifugal sedimentation type particle size distribution measuring device is used to measure the volumetric particle size distribution of MWCNT under the following measurement conditions. In the measured volumetric particle size distribution, the particle size at which the cumulative frequency is 50% is read and taken as the median size. As the centrifugal sedimentation type particle size distribution measuring device, for example, LUMiSizer 611 (product name), which is a centrifugal sedimentation type dispersion stability particle size distribution measuring device manufactured by LUM GmbH, can be suitably used. However, the centrifugal sedimentation type particle size distribution measuring device is not limited to these.

[0044] <Measurement conditions> Measurement cell: Polycarbonate cell (optical path length: 2 mm) Rotational speed: 4000 rpm Centrifugal acceleration: 2300×g Measurement interval: 30 seconds Number of measurements: 1000 Measurement temperature: 25℃

[0045] The above median diameter can be controlled by the synthesis conditions, such as the firing temperature, gas flow rate, and gas introduction method, when synthesizing the MWCNTs. The median diameter can be increased, for example, by increasing the firing temperature during synthesis of the MWCNTs, and can be decreased, for example, by decreasing the firing temperature during synthesis of the MWCNTs.

[0046] The MWCNT aggregate (A) according to the present disclosure contains MWCNTs whose rate of change in transmittance measured by centrifugal sedimentation method is 0.3% / hour or less when the MWCNTs are dispersed in water at a concentration of 0.2% by mass. When the rate of change in the transmittance of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is 0.3% / hour or less, the stability of the MWCNT aggregate (A) in an aqueous dispersion can be improved, and the electrical conductivity can be improved. The rate of change in the transmittance of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is preferably 0.25% / hour or less, more preferably 0.2% / hour or less, and even more preferably 0.15% / hour or less. The lower limit of the rate of change in the transmittance of the MWCNTs contained in the MWCNT aggregate (A) according to the present disclosure is not particularly limited, but from the viewpoint of ease of production, for example, it is preferably 0.01% / hour or more, and more preferably 0.03% / hour or more.

[0047] In the present disclosure, the rate of change in transmittance measured by centrifugal sedimentation when MWCNT is dispersed in water at a concentration of 0.2% by mass is determined by the following method. MWCNT and a dispersant are added to ion-exchanged water, and then a dispersion process is performed to obtain an aqueous dispersion of MWCNT. The amount of MWCNT added is such that the concentration of MWCNT in the aqueous dispersion becomes 0.2 mass%. The obtained aqueous dispersion is used as a measurement sample, and a centrifugal sedimentation type particle size distribution measurement device is used to obtain a sedimentation profile under the following measurement and analysis conditions. The rate of change in the overall transmittance is analyzed from the obtained sedimentation profile to determine the rate of change in the transmittance. As the centrifugal sedimentation type particle size distribution measuring device, for example, LUMiSizer 611 (product name), which is a centrifugal sedimentation type dispersion stability particle size distribution measuring device manufactured by LUM GmbH, can be suitably used. However, the centrifugal sedimentation type particle size distribution measuring device is not limited to these.

[0048] <Measurement / analysis conditions> Measurement cell: Polycarbonate cell (optical path length: 2 mm) Rotational speed: 4000 rpm Centrifugal acceleration: 2300×g Measurement interval: 30 seconds Number of measurements: 1000 Dispersion medium viscosity: 0.8946 mPa s Density of dispersion medium: 997.3kg / m 3 Density of dispersoid: 1350kg / m 3 Refractive index of dispersion medium (real part): 1.326 Refractive index of dispersoid (real part): 1.630 Refractive index of dispersion medium (imaginary part): 0.5153 Under the above analysis conditions, the dispersion medium is water and the dispersoid is MWCNT. The above viscosity, density and refractive index values ​​are all values ​​at 25°C.

[0049] The rate of change in the transmittance can be controlled by the synthesis conditions, such as the firing temperature, gas flow rate, and gas introduction method, during synthesis of the MWCNTs. The rate of change in the transmittance can be increased by, for example, increasing the gas flow rate during synthesis of the MWCNTs, and can be decreased by decreasing the gas flow rate during synthesis of the MWCNTs.

[0050] [MWCNT aggregate (B)] When the MWCNT aggregate (B) according to the present disclosure is dispersed in water at a concentration of 0.2 mass%, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q=0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The MWCNTs include MWCNTs having a scattering intensity ratio S1 / S2 of 90 or more, which is the ratio of the scattering intensity S1 to the scattering intensity S2 in the MWCNT.

[0051] The MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure preferably have a fibrous shape, from the viewpoint of facilitating the formation of a network structure through entanglement of the MWCNTs with each other.

[0052] The maximum length of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is not particularly limited, but is, for example, preferably 500 μm to 30,000 μm, more preferably 1,000 μm to 25,000 μm, even more preferably 1,100 μm to 20,000 μm, particularly preferably 1,200 μm to 18,000 μm, and especially preferably 1,300 μm to 15,000 μm. When the maximum length of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is 500 μm or more, the electrical conductivity of the MWCNT aggregate (B) tends to be higher. This is thought to be because the MWCNTs contained in the MWCNT aggregate (B) are more likely to come into contact with each other, making it easier to form a conductive path. The MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure tend to be easier to produce when the maximum length is 30000 μm or less.

[0053] The MWCNT aggregate (B) according to the present disclosure preferably contains one or more MWCNTs having a maximum length of 500 μm to 30,000 μm (that is, SLMWCNTs), and more preferably contains a plurality of MWCNTs.

[0054] The proportion of SLMWCNTs in the MWCNT aggregate (B) according to the present disclosure is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more, based on the number of pieces. When the ratio of SLMWCNTs in the MWCNT aggregate (B) according to the present disclosure is 10% or more on a number basis, the stability of the MWCNT aggregate (B) in an aqueous dispersion due to entanglement of the MWCNTs tends to be further improved.

[0055] The diameter of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is not particularly limited, but is, for example, preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, further preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0056] The ratio of length to diameter (so-called aspect ratio) of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is preferably 1000 or more, more preferably 3000 or more, further preferably 5000 or more, and particularly preferably 10000 or more.

[0057] The specific gravity of the MWCNT aggregate (B) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, it is preferably 1.5 to 2.5, more preferably 1.7 to 2.4, and even more preferably 1.8 to 2.2.

[0058] The MWCNT aggregate (B) according to the present disclosure contains MWCNTs having a scattering intensity ratio S1 / S2 of 90 or more in a scattering profile obtained by small-angle X-ray scattering when dispersed in water at a concentration of 0.2% by mass. When the scattering intensity ratio S1 / S2 of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is 90 or more, the electrical conductivity of the MWCNT aggregate (B) can be improved. The scattering intensity ratio S1 / S2 of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is preferably 95 or more, more preferably 98 or more, even more preferably 100 or more, and particularly preferably 110 or more. The upper limit of the scattering intensity ratio S1 / S2 of the MWCNTs contained in the MWCNT aggregate (B) according to the present disclosure is not particularly limited, but from the viewpoint of ease of production, for example, it is preferably 250 or less, and more preferably 200 or less.

[0059] The scattering intensity ratio S1 / S2 can be controlled by the synthesis conditions, such as the firing temperature, gas flow rate, and gas introduction method, when synthesizing the MWCNTs. The scattering intensity ratio S1 / S2 can be increased, for example, by increasing the firing temperature during synthesis of the MWCNTs, and can be decreased, for example, by decreasing the firing temperature during synthesis of the MWCNTs.

[0060] [MWCNT aggregate (C)] When the MWCNT aggregate (C) according to the present disclosure is dispersed in water at a concentration of 0.2 mass%, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is q=0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 The MWCNTs include MWCNTs having a scattering intensity ratio S3 / S4 of 10 or less, which is the ratio of the scattering intensity S3 to the scattering intensity S4 in the MWCNT.

[0061] The MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure preferably have a fibrous shape, from the viewpoint of facilitating the formation of a network structure through entanglement of the MWCNTs with each other.

[0062] The maximum length of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is not particularly limited, but is, for example, preferably 500 μm to 30,000 μm, more preferably 1,000 μm to 25,000 μm, even more preferably 1,100 μm to 20,000 μm, particularly preferably 1,200 μm to 18,000 μm, and especially preferably 1,300 μm to 15,000 μm. When the maximum length of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is 500 μm or more, the electrical conductivity of the MWCNT aggregate (C) tends to be higher. This is thought to be because the MWCNTs contained in the MWCNT aggregate (C) are more likely to come into contact with each other, making it easier to form a conductive path. The MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure tend to be easier to produce when the maximum length is 30000 μm or less.

[0063] The MWCNT aggregate (C) according to the present disclosure preferably contains one or more MWCNTs having a maximum length of 500 μm to 30,000 μm (that is, SLMWCNTs), and more preferably contains a plurality of MWCNTs.

[0064] The proportion of SLMWCNTs in the MWCNT aggregate (C) according to the present disclosure is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more, based on the number of pieces. When the ratio of SLMWCNTs in the MWCNT aggregate (C) according to the present disclosure is 10% or more on a number basis, the stability of the MWCNT aggregate (C) in an aqueous dispersion due to entanglement of the MWCNTs tends to be further improved.

[0065] The diameter of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is not particularly limited, but is, for example, preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, further preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0066] The ratio of length to diameter (so-called aspect ratio) of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is preferably 1000 or more, more preferably 3000 or more, further preferably 5000 or more, and particularly preferably 10000 or more.

[0067] The specific gravity of the MWCNT aggregate (C) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, it is preferably 1.5 to 2.5, more preferably 1.7 to 2.4, and even more preferably 1.8 to 2.2.

[0068] The MWCNT aggregate (C) according to the present disclosure contains MWCNTs in which the scattering intensity ratio S3 / S4 of the scattering profile obtained by small-angle X-ray scattering is 10 or less when the MWCNTs are dispersed in water at a concentration of 0.2% by mass. When the scattering intensity ratio S3 / S4 of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is 10 or less, the electrical conductivity of the MWCNT aggregate (C) can be improved. The scattering intensity ratio S3 / S4 of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is preferably 9.5 or less, more preferably 9 or less, and even more preferably 8.5 or less. The lower limit of the scattering intensity ratio S3 / S4 of the MWCNTs contained in the MWCNT aggregate (C) according to the present disclosure is not particularly limited, but from the viewpoint of ease of production, for example, it is preferably 1 or more, and more preferably 4 or more.

[0069] The scattering intensity ratio S3 / S4 can be controlled by the synthesis conditions such as the firing temperature, gas flow rate, and gas introduction method when synthesizing the MWCNTs. The scattering intensity ratio S3 / S4 can be increased, for example, by increasing the gas flow rate during synthesis of MWCNTs, and can be decreased, for example, by decreasing the gas flow rate during synthesis of MWCNTs.

[0070] In this disclosure, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering when MWCNT is dispersed in water at a concentration of 0.2 mass % is q = 0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The scattering intensity ratio S1 / S2, which is the ratio of the scattering intensity S1 at 0.02 nm to the scattering intensity S2 at 0.02 nm, and the magnitude of the scattering vector q of the scattering profile obtained by small-angle X-ray scattering -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 The scattering intensity ratio S3 / S4, which is the ratio of the scattering intensity S3 to the scattering intensity S4 at S3, is determined by the following method. After adding MWCNT and a dispersant to ion-exchanged water, a dispersion process is performed to obtain an aqueous dispersion of MWCNT. The amount of MWCNT added is an amount that results in a concentration of MWCNT of 0.2 mass% when the aqueous dispersion is obtained. The obtained aqueous dispersion is used as a measurement sample. The measurement sample is packed into an NMR tube (product name: S-3-HT-7, manufactured by NORELL) with an outer diameter of 2.99±0.03 mm and an inner diameter of 2.41±0.03 mm while being careful not to trap bubbles, and then a scattering profile of the MWCNT is obtained using a small-angle X-ray scattering device. Measurements using small-angle X-ray scattering are performed in accordance with the description in "Structural Science of Crystalline Polymers, Kohji Tashiro, Springer, 2022." More specifically, X-rays are incident on the axial center of the NMR tube in a direction perpendicular to the length direction. The exposure time is 1 second, and the irradiation position is changed in the length direction by 100 μm at a time, and 10 measurements are taken to obtain a total two-dimensional scattering image Ms. At the same time as taking the two-dimensional scattering image, the transmitted light intensity fs is measured in the ion chamber downstream of the NMR tube. The background two-dimensional scattering image Mb and transmitted light intensity fb are measured under the same conditions as above, except that the NMR tube is filled with ion-exchanged water instead of the aqueous dispersion. A two-dimensional scattered image M after background correction is obtained using the following formula (1). At this time, the area where the scattered X-rays are blocked by a beam stopper or the like installed to prevent the direct beam from entering the detector is excluded from the two-dimensional scattered image M. M = Ms / fs-Mb / fb (1) A one-dimensional radial profile is obtained by circular averaging from the two-dimensional scattering image M. The horizontal axis is calibrated to the magnitude q of the scattering vector using collagen, a standard material. From the obtained one-dimensional profile, the magnitude of the scattering vector q = 0.2 nm -1 Scattering intensity S1 at q = 0.8 nm -1 Scattering intensity S2 at q = 0.02 nm -1 Scattering intensity S3 and the magnitude of the scattering vector q at 0.08 nm -1 The scattering intensity ratio S1 / S2 and the scattering intensity ratio S3 / S4 are calculated. As the small-angle X-ray scattering experimental equipment, for example, the beamline BL03XU of SPring-8, which is a large-scale synchrotron radiation facility, can be suitably used. However, the small-angle X-ray scattering experimental equipment is not limited to this. Also, instead of a large-scale synchrotron radiation facility, for example, NANOPIX (product name), which is a small-angle X-ray scattering device manufactured by Rigaku Corporation, may be used. The wavelength of the X-ray is preferably 0.03 nm to 0.13 nm. The beam diameter is preferably 1 μm to 100 μm. The measurement temperature is preferably 20° C. to 30° C. The camera length is preferably 8000 mm. However, the magnitude of the scattering vector q=0.2 nm. -1 and the magnitude of the scattering vector q = 0.8 nm -1 The camera length is, for example, 700 mm to 8000 mm, and the scattering vector magnitude q = 0.02 nm. -1 and the magnitude of the scattering vector q = 0.08 nm -1 Measurements of camera lengths including the above, for example, 8000 mm to 20000 mm, may be performed separately. As a detector, for example, Pilatus 1M (product name) manufactured by Dectris can be suitably used, although the detector is not limited thereto.

[0071] Preferable aspects of the multi-walled carbon nanotube aggregate according to the present disclosure include the following aspects 1, 2, and 3. Details of the requirements in aspects 1, 2, and 3 are similar to the details of the requirements in the aspects of the MWCNT aggregate (A), the MWCNT aggregate (B), and the MWCNT aggregate (C).

[0072] A preferred embodiment 1 of the multi-walled carbon nanotube aggregate according to the present disclosure is such that, when the aggregate is made into an aqueous dispersion of 0.004 mass%, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more, when the aggregate is made into an aqueous dispersion of 0.2 mass%, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less, and when the aggregate is made into an aqueous dispersion of 0.2 mass%, the magnitude of the scattering vector of the scattering profile obtained by small-angle X-ray scattering is q=0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 In this embodiment, the multi-walled carbon nanotube has a scattering intensity ratio S1 / S2 of 90 or more, which is the ratio of the scattering intensity S1 to the scattering intensity S2 in the multi-walled carbon nanotube. Aspect 1 is an aspect in which the aspect of the MWCNT aggregate (A) according to the present disclosure and the aspect of the MWCNT aggregate (B) according to the present disclosure are combined.

[0073] A preferred embodiment 2 of the multi-walled carbon nanotube aggregate according to the present disclosure is such that, when the aggregate is made into an aqueous dispersion of 0.004 mass%, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more, when the aggregate is made into an aqueous dispersion of 0.2 mass%, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less, and when the aggregate is made into an aqueous dispersion of 0.2 mass%, the magnitude of the scattering vector of the scattering profile obtained by small-angle X-ray scattering is q=0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 In this embodiment, the multi-walled carbon nanotubes have a scattering intensity ratio S3 / S4 of 10 or less, which is the ratio of the scattering intensity S3 to the scattering intensity S4 in the multi-walled carbon nanotubes. Aspect 2 is a combination of the aspect of the MWCNT aggregate (A) according to the present disclosure and the aspect of the MWCNT aggregate (C) according to the present disclosure.

[0074] In a preferred embodiment 3 of the multi-walled carbon nanotube aggregate according to the present disclosure, when the aggregate is dispersed in water at a concentration of 0.2 mass %, the magnitude of the scattering vector of the scattering profile obtained by the small angle X-ray scattering method is q=0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 The scattering intensity ratio S1 / S2, which is the ratio of the scattering intensity S1 to the scattering intensity S2 in the scattering profile, is 90 or more, and the magnitude q of the scattering vector in the scattering profile is 0.02 nm -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 In this embodiment, the multi-walled carbon nanotubes have a scattering intensity ratio S3 / S4 of 10 or less, which is the ratio of the scattering intensity S3 to the scattering intensity S4 in the multi-walled carbon nanotubes. Aspect 3 is an aspect in which the aspect of the MWCNT aggregate (B) according to the present disclosure and the aspect of the MWCNT aggregate (C) according to the present disclosure are combined.

[0075] [MWCNT aggregate (D)] In an embodiment, the multi-walled carbon nanotube aggregate according to the present disclosure includes multi-walled carbon nanotubes having a maximum length of 1000 μm to 30000 μm, a peak intensity ratio G1 / D1, which is a ratio of a peak intensity G1 of a G band to a peak intensity D1 of a D band in a Raman spectrum of the multi-walled carbon nanotubes, is more than 0.9 and 15 or less, and a BET specific surface area of ​​the multi-walled carbon nanotubes is 50 m 2 / g~400m 2 / g. In the present disclosure, the multi-walled carbon nanotube aggregate according to this embodiment is also referred to as "MWCNT aggregate (D)." In addition, in the present disclosure, "MWCNT having a maximum length of 1000 μm to 30000 μm" is also referred to as "ULMWCNT."

[0076] The MWCNT aggregate (D) according to the present disclosure has high electrical conductivity. The reason why the MWCNT aggregate (D) according to the present disclosure has high electrical conductivity is not clear, but the present inventors speculate as follows. However, the following speculation is not intended to limit the MWCNT aggregate (D) according to the present disclosure, but is described as an example.

[0077] Since the MWCNT aggregate (D) according to the present disclosure contains MWCNTs (i.e., ULMWCNTs) with a maximum length of 1000 μm to 30000 μm, it is considered that the MWCNTs are likely to come into contact with each other. When the MWCNTs are likely to come into contact with each other, a conductive path is likely to be formed, and the conductivity can be improved. In addition, the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure have a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum, of a specific value or more, and have relatively few defects in the MWCNTs. The fewer the defects in the MWCNTs, the more the conductivity can be improved. In addition, the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure have the above peak intensity ratio G1 / D1 of a specific value or less, and are relatively non-uniform in shape, so that the MWCNTs tend to be easily entangled with each other. The more the MWCNTs are entangled with each other, the more the conductivity can be improved. Furthermore, since the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure have a moderately large BET specific surface area, it is believed that the MWCNTs come into close contact with each other. When the MWCNTs come into close contact with each other, the volume resistivity of the MWCNTs decreases, and the electrical conductivity can be improved. From the above, it is presumed that the MWCNT aggregate (D) according to the present disclosure has high electrical conductivity.

[0078] The ULMWCNTs contained in the MWCNT aggregate (D) according to the present disclosure may have a fibrous shape. The ULMWCNTs have the property of easily entangling with each other when they have a fibrous shape. For this reason, in the MWCNT aggregate (D) according to the present disclosure, a network structure is easily formed by the entanglement of the MWCNTs.

[0079] The MWCNT aggregate (D) according to the present disclosure includes MWCNTs having a maximum length of 1000 μm to 30000 μm (that is, ULMWCNTs). ULMWCNTs are longer than general-purpose MWCNTs. The MWCNT aggregate (D) according to the present disclosure tends to have higher electrical conductivity by including MWCNTs having a maximum length of 1000 μm or more. The reason for this is believed to be that the MWCNTs included in the MWCNT aggregate (D) are more likely to come into contact with each other, making it easier to form a conductive path. The MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure tend to be easier to produce when the maximum length is 30000 μm or less. The MWCNT aggregate (D) according to the present disclosure preferably contains MWCNTs having a maximum length of 1050 μm to 25000 μm, more preferably contains MWCNTs having a maximum length of 1100 μm to 20000 μm, further preferably contains MWCNTs having a maximum length of 1200 μm to 18000 μm, and particularly preferably contains MWCNTs having a maximum length of 1300 μm to 15000 μm.

[0080] The MWCNT aggregate (D) according to the present disclosure contains at least one MWCNT having a maximum length of 1000 μm to 30000 μm (that is, ULMWCNT), and preferably contains a plurality of MWCNTs. The proportion of ULMWCNTs in the MWCNT aggregate (D) according to the present disclosure is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more, on a number basis. When the ratio of ULMWCNTs in the MWCNT aggregate (D) according to the present disclosure is 10% or more on a number basis, the stability of the MWCNT aggregate (D) in an aqueous dispersion due to entanglement of the MWCNTs tends to be further improved.

[0081] The diameter of the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is not particularly limited, but is, for example, preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, further preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0082] The ratio of length to diameter (so-called aspect ratio) of the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is preferably 1000 or more, more preferably 3000 or more, further preferably 5000 or more, and particularly preferably 10000 or more.

[0083] The specific gravity of the MWCNT aggregate (D) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, it is preferably 1.5 to 2.5, more preferably 1.7 to 2.4, and even more preferably 1.8 to 2.2.

[0084] The MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure have a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in a Raman spectrum, of more than 0.9 and 15 or less, preferably 1.0 or more and 14 or less, more preferably 1.2 or more and 13 or less, even more preferably 1.3 or more and 12 or less, and particularly preferably 1.5 or more and 12 or less. When the peak intensity ratio G1 / D1 of the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure exceeds 0.9, the number of defects present in the MWCNTs decreases, and electrical conductivity tends to improve. When the peak intensity ratio G1 / D1 of the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is 15 or less, the uniformity of the shape is disturbed, and the MWCNTs tend to easily become entangled with each other.

[0085] In the present disclosure, the peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum of MWCNT, is determined by the following method. Using a Raman spectrometer, a Raman spectrum of the MWCNT is obtained under the following measurement conditions. From the obtained Raman spectrum, the peak intensity G1 of the G band and the peak intensity D1 of the D band are read, and the peak intensity ratio G1 / D1 is calculated. As the Raman spectrometer, for example, a Raman spectrometer, RAMAN-11 (product name), manufactured by Nanophoton Co., Ltd., can be suitably used. However, the Raman spectrometer is not limited to this.

[0086] <Measurement conditions> Excitation laser wavelength: 532 nm Grating: 600 grooves / mm Objective lens: 20x, numerical aperture (NA) 0.45

[0087] In this disclosure, the peak intensity G1 of the G band in the Raman spectrum is 1550 cm -1 ~1600cm -1 In the present disclosure, the peak intensity D1 of the D band in the Raman spectrum refers to the maximum scattering intensity at a Raman shift of 1300 cm -1 ~1400cm -1 This refers to the maximum scattering intensity at a Raman shift of

[0088] The peak intensity ratio G1 / D1, which is the ratio of the G band peak intensity G1 to the D band peak intensity D1 in the Raman spectrum of MWCNT, can be controlled by the synthesis conditions such as the firing temperature, gas flow rate, and gas introduction method when synthesizing MWCNT. The peak intensity ratio G1 / D1 can be increased by, for example, increasing the firing temperature during synthesis of the MWCNTs, and can be decreased by decreasing the firing temperature during synthesis of the MWCNTs.

[0089] The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is 50 m 2 / g~400m 2 / g, 60m 2 / g~350m 2 / g, and 70m 2 / g~300m 2 / g is more preferable, and 80m 2 / g~280m 2 More preferably, it is 100m2 / g~250m 2 It is particularly preferred that the molecular weight is 1 / g. The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is 50 m 2 / g or more, the electrical conductivity of the MWCNT aggregate (D) tends to increase. This is thought to be because the MWCNTs come into close contact with each other, decreasing the volume resistivity of the MWCNTs. The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (D) according to the present disclosure is 400 m 2 When the molecular weight is 1 / g or less, the MWCNTs are less likely to aggregate in the aqueous dispersion, and the dispersibility of the MWCNTs tends to increase.

[0090] In the present disclosure, the BET specific surface area of ​​MWCNT is determined by a gas adsorption method using nitrogen gas in accordance with JIS Z 8830:2013. Specifically, MWCNT is packed into a sample tube, and the sample tube is vacuum degassed at 300°C for 3 hours using a pretreatment device, thereby pretreating the MWCNT. The pretreated MWCNT is used as a measurement sample, and the amount of nitrogen adsorption of MWCNT is measured using a specific surface area measurement device under the following measurement conditions, to obtain an adsorption / desorption isotherm. The BET specific surface area is determined from the obtained adsorption / desorption isotherm under the following analysis conditions. As the specific surface area measuring device and the pretreatment device, for example, BELSORP-mini II (product name), which is a specific surface area measuring device manufactured by Microtrack-Bell Co., Ltd., and BELPREP-vacII (product name), which is a pretreatment device manufactured by Microtrack-Bell Co., Ltd., can be suitably used. However, the specific surface area measuring device and the pretreatment device are not limited thereto.

[0091] <Measurement / analysis conditions> Measurement method: constant volume method Adsorption temperature: 77K Adsorbate: Nitrogen Saturated vapor pressure: Actual measurement Equilibration time: 500 sec Specific surface area: BET method (BET-Plot)

[0092] The BET specific surface area of ​​MWCNT can be controlled by the synthesis conditions, such as the firing temperature, gas flow rate, and gas introduction method, during synthesis of MWCNT. The BET specific surface area of ​​MWCNT can be increased, for example, by increasing the firing temperature during synthesis of MWCNT, and can be decreased, for example, by decreasing the firing temperature during synthesis of MWCNT.

[0093] The MWCNT aggregate (D) according to the present disclosure may contain MWCNTs other than ULMWCNTs, as long as the effect of the MWCNTs is not impaired. The MWCNTs other than ULMWCNTs may be MWCNTs having a maximum length of less than 1000 μm, or may be MWCNTs having a maximum length of more than 30000 μm.

[0094] Furthermore, the MWCNT aggregate (D) according to the present disclosure may contain MWCNTs having a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in a Raman spectrum, of 0.9 or less, and may contain more than 15 MWCNTs, within a range that does not impair the effects of the MWCNT aggregate (D).

[0095] In addition, the MWCNT aggregate (D) according to the present disclosure has a BET specific surface area of ​​50 m within a range that does not impair the effect. 2 / g MWCNTs, 2 The composition may contain more than 1000 MWCNTs / g.

[0096] [MWCNT aggregate (E)] In an embodiment, the multi-walled carbon nanotube aggregate according to the present disclosure includes multi-walled carbon nanotubes having a maximum length of more than 1600 μm and not more than 30000 μm, and the multi-walled carbon nanotubes have a peak intensity ratio G1 / D1 of 10 or less, which is a ratio of a peak intensity G1 of a G band to a peak intensity D1 of a D band in a Raman spectrum of the multi-walled carbon nanotubes, and the multi-walled carbon nanotubes have a BET specific surface area of ​​200 m 2 / g~300m 2 / g. In the present disclosure, the multi-walled carbon nanotube aggregate according to this embodiment is also referred to as "MWCNT aggregate (E)." In addition, in the present disclosure, "MWCNTs having a maximum length of 1600 μm to 30000 μm" is also referred to as "specific ULMWCNTs."

[0097] The MWCNT aggregate (E) according to the present disclosure has high electrical conductivity. The reason why the MWCNT aggregate (E) according to the present disclosure has high electrical conductivity is not clear, but the present inventors speculate as follows. However, the following speculation is not intended to limit the MWCNT aggregate (E) according to the present disclosure, but is provided as an example.

[0098] Since the MWCNT aggregate (E) according to the present disclosure contains MWCNTs with a maximum length of 1600 μm to 30000 μm (i.e., specific ULMWCNTs), it is considered that the MWCNTs are likely to come into contact with each other. When the MWCNTs are likely to come into contact with each other, a conductive path is likely to be formed, and the conductivity can be improved. Furthermore, the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure have a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum, that is equal to or less than a specific value, and have a relatively non-uniform shape, so that the MWCNTs tend to be easily entangled with each other. The more entanglements between the MWCNTs occur, the more the conductivity can be improved. Furthermore, since the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure have a moderately large BET specific surface area, it is considered that the MWCNTs are in close contact with each other. When the MWCNTs are in close contact with each other, the surface resistivity of the MWCNTs decreases, and the conductivity can be improved. From the above, it is presumed that the MWCNT aggregate (E) according to the present disclosure has high electrical conductivity.

[0099] The specific ULMWCNT contained in the MWCNT aggregate (E) according to the present disclosure may have a fibrous shape. The specific ULMWCNT has a property of easily entangling with each other by taking the fibrous shape. Therefore, in the MWCNT aggregate (E) according to the present disclosure, a network structure is easily formed by the entanglement of the MWCNTs.

[0100] The MWCNT aggregate (E) according to the present disclosure contains MWCNTs having a maximum length of 1600 μm to 30000 μm (i.e., specific ULMWCNTs). The specific ULMWCNTs are extremely long compared to general-purpose MWCNTs. The MWCNT aggregate (E) according to the present disclosure tends to have higher electrical conductivity by including MWCNTs having a maximum length of 1600 μm or more. This is thought to be because the MWCNTs included in the MWCNT aggregate (E) tend to come into contact with each other, making it easier to form a conductive path. The MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure tend to be easier to produce when the maximum length is 30000 μm or less. The MWCNT aggregate (E) according to the present disclosure preferably contains MWCNTs having a maximum length of 1700 μm to 25000 μm, more preferably contains MWCNTs having a maximum length of 1800 μm to 20000 μm, further preferably contains MWCNTs having a maximum length of 1900 μm to 18000 μm, and particularly preferably contains MWCNTs having a maximum length of 2000 μm to 15000 μm.

[0101] The MWCNT aggregate (E) according to the present disclosure contains at least one MWCNT having a maximum length of 1600 μm to 30000 μm (that is, specific ULMWCNT), and preferably contains a plurality of MWCNTs. The ratio of the specific ULMWCNTs in the MWCNT aggregate (E) according to the present disclosure is, for example, preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, and particularly preferably 50% or more, based on the number of pieces. When the ratio of the specific ULMWCNTs in the MWCNT aggregate (E) according to the present disclosure is 10% or more on a number basis, the stability of the MWCNT aggregate (E) in an aqueous dispersion due to entanglement of the MWCNTs tends to be further improved.

[0102] The diameter of the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is not particularly limited, but is, for example, preferably 1 nm to 100 nm, more preferably 2 nm to 80 nm, further preferably 3 nm to 50 nm, and particularly preferably 5 nm to 30 nm.

[0103] The ratio of length to diameter (so-called aspect ratio) of the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is preferably 1000 or more, more preferably 3000 or more, further preferably 5000 or more, and particularly preferably 10000 or more.

[0104] The specific gravity of the MWCNT aggregate (E) according to the present disclosure is not particularly limited, but from the viewpoint of dispersibility when made into an aqueous dispersion, it is preferably 1.5 to 2.5, more preferably 1.7 to 2.4, and even more preferably 1.8 to 2.2.

[0105] The MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure have a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in a Raman spectrum, of 10 or less, preferably 9 or less, and more preferably 8 or less. When the peak intensity ratio G1 / D1 of the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is 10 or less, the uniformity of the shape is disturbed, and the MWCNTs tend to easily become entangled with each other. The lower limit of the above peak intensity ratio G1 / D1 of the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is not particularly limited, but from the viewpoint of improving electrical conductivity by reducing defects present in the MWCNTs, for example, it is preferably 1 or more, more preferably 1.5 or more, and even more preferably 2 or more. The peak intensity ratio G1 / D1 of the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure may be, for example, 1-10, 1.5-9, or 2-8.

[0106] The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is 200 m 2 / g~300m 2 / g, 205m 2 / g~290m 2 / g, and 210m 2 / g~280m 2 / g is more preferable, and 220m 2 / g~275m 2 It is more preferable that the molecular weight is / g. The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is 200 m 2 / g or more, the electrical conductivity of the MWCNT aggregate (E) tends to increase. This is thought to be because the contact between the MWCNTs becomes denser, which reduces the surface resistivity of the MWCNTs. The BET specific surface area of ​​the MWCNTs contained in the MWCNT aggregate (E) according to the present disclosure is 300 m 2 When the molecular weight is 1 / g or less, the MWCNTs are less likely to aggregate in the aqueous dispersion, and the dispersibility of the MWCNTs tends to increase.

[0107] The BET specific surface area of ​​MWCNT can be controlled by the synthesis conditions, such as the firing temperature, gas flow rate, and gas introduction method, during synthesis of MWCNT. The BET specific surface area of ​​MWCNT can be increased by, for example, increasing the firing temperature during synthesis of MWCNT, and can be decreased by decreasing the firing temperature.

[0108] The MWCNT aggregate (E) according to the present disclosure may contain MWCNTs other than the specific ULMWCNTs, as long as the effect of the MWCNTs is not impaired. The MWCNTs other than the specific ULMWCNTs may be MWCNTs having a maximum length of less than 1600 μm, or may be MWCNTs having a maximum length of more than 30000 μm.

[0109] Furthermore, the MWCNT aggregate (E) according to the present disclosure may contain MWCNTs having a peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum, of more than 10, within a range that does not impair the effects of the MWCNT aggregate (E).

[0110] In addition, the MWCNT aggregate (E) according to the present disclosure has a BET specific surface area of ​​200 m within a range that does not impair the effect. 2 / g MWCNTs, 2 The composition may contain more than 1000 MWCNTs / g.

[0111] <<Applications of multi-walled carbon nanotube aggregates>> The use of the MWCNT aggregate according to the present disclosure is not particularly limited. The MWCNT aggregate according to the present disclosure has high electrical conductivity and can therefore be suitably used, for example, as a conductive assistant (particularly, a conductive assistant for negative electrodes). In the MWCNT aggregate according to the present disclosure, the MWCNTs are easily entangled with each other to form conductive paths. Therefore, for example, by coexisting with conductive materials such as a positive electrode active material and a negative electrode active material in an electrode, the conductivity of the conductive material can be further improved. The MWCNT aggregate according to the present disclosure can be used together with, for example, known conductive assistants such as graphite and Ketjen black.

[0112] The MWCNT aggregate according to the present disclosure can be used, for example, as a conductive material. Examples of conductive materials to which the MWCNT aggregate according to the present disclosure is applied include electrode materials in secondary batteries (e.g., lithium ion batteries), specifically, negative and positive electrode materials.

[0113] [Method of manufacturing multi-walled carbon nanotubes] There is no particular limitation on the method for producing MWCNTs contained in the MWCNT aggregate according to the present disclosure (so-called MWCNTs in the present disclosure).

[0114] As a method for producing MWCNT in the present disclosure, a conventionally known method such as a chemical vapor deposition (CVD) method or a method of reacting a gaseous reactant containing a carbon source in the presence of a catalyst can be applied.

[0115] The MWCNTs in the present disclosure can be produced, for example, by referring to the production method described in JP 2016-102047 A. Hereinafter, the method for producing MWCNTs according to the present disclosure will be described with reference to an example, however, the method for producing MWCNTs according to the present disclosure is not limited to the following example.

[0116] An example of a method for producing MWCNTs in the present disclosure is the method described in JP 2016-102047 A, i.e., a production method (also referred to as "production method X") that includes the steps of passing a gaseous reactant containing one or more carbon sources into a reactor, reacting the one or more gaseous reactants in a reaction zone of the reactor in the presence of a catalyst to form product particles containing carbon, agglomerating the product particles into agglomerates, and applying a force to the agglomerates to continuously move the agglomerates out of the reaction zone. According to the manufacturing method X, the MWCNTs of the present disclosure can be obtained in the form of fibrous aggregates or other aggregate forms that are easy to handle.

[0117] In the manufacturing method X, the force applied to the product particles may be a mechanical force. When the agglomerates are fibrous MWCNTs, the mechanical force applied to the product particles can be exerted by a rotating spindle around which the agglomerates are wound. The fibrous MWCNTs can be collected on the spindle or can be accumulated elsewhere by successively unwinding the spindle after one or more revolutions around the spindle.

[0118] The spindle is preferably oriented with the spindle axis perpendicular or parallel to the flow direction of the gaseous reactant(s), but may be oriented at other orientations, for example a spindle with the spindle axis oriented at an angle of 25° to the flow direction of the gaseous reactants may also be suitable for applying mechanical forces to the product particles.

[0119] The spindle can rotate about two axes (e.g., two perpendicular axes). In particular, the spindle can rotate about axes perpendicular and parallel to the flow direction of the gaseous reactants. Such a spindle can pull and twist the fibrous MWCNT aggregates to control the number and length of twists.

[0120] The spindle may be made of metal, ceramic, or plastic. The spindle can have different suitable shapes depending on the material properties and the intended use of the MWCNTs. The spindle can be used as a mold for producing carbon products, for example, by a spin-coating process. The preferred spindle shape is rod-shaped or box-shaped.

[0121] Fibrous MWCNTs are deposited on a spindle or elsewhere, and the coating thickness and its orientation can be controlled by controlling the reaction time and conditions, or by the conditions under which an electric or other field is applied to the carbon product. Coating thickness and its orientation can be controlled, for example, by gas flow forces.

[0122] The rotation speed of the spindle is preferably 0.01 rpm (revolutions / minute; the same applies below) to 10,000 rpm, and more preferably 0.1 rpm to 100 rpm. The spinning speed (i.e., the rotational speed of the spindle) may be adjusted so that material is collected at a similar rate as it is produced. The rotational speed of the spindle may control the thickness of the accumulated MWCNT fiber. In a preferred embodiment, as the spindle rotates, the MWCNT fiber is processed in the axial direction of the spindle, such that the MWCNT fiber is wrapped evenly along the spindle, rather than only at one particular point on the spindle.

[0123] The MWCNT fibers may be collected, for example, on the reactor wall by a substrate placed in the reactor. The substrate may be a fixed substrate or a rotating guide that is used to apply a strong and equal force to the MWCNT fibers as they are collected. Suitable substrate configurations for fiber technology include a substrate consisting of two guides positioned at right angles to each other.

[0124] In process X, the mechanical force applied to the product particles may be a force applied by an accelerating gas flow. The accelerating gas flow may be generated by passing the product particles through a reactor having a narrow diameter or through a capillary tube downstream of the reaction zone. A vacuum may be applied to the product particles.

[0125] Other forces that can be applied to the product particles include electrostatic forces, suitably applied by charged plates. Electrostatic forces require that the product particles be charged. The use of charged plates allows the MWCNTs to form in an entangled mat on the charged plates.

[0126] Other forces applied to the product particles may also be magnetic forces or photon pressure applied by a light source.

[0127] The CNT source may be injected in the form of a liquid containing a carbon source instead of a gaseous reactant containing a carbon source. When a liquid is used as the CNT source, it can be injected through a single inlet or multiple inlets, for example in a showerhead arrangement.

[0128] The gaseous reactant or reactants are preferably reacted at between 500° C. and 1600° C., more preferably between 1000° C. and 1500° C. or 1600° C. (particularly between 1000° C. and 1500° C.). A temperature gradient is preferably maintained within the reactor, with the reaction zone being maintained at a higher temperature than the product zone of the reactor.

[0129] The gaseous reactants may be mixed with one or more gases that act as diluents. The gaseous reactants may be mixed with gases that do not play a direct role in the reaction but play a supporting role. It is also preferred to use a diluent gas that can react with the amorphous carbon by-product to keep the reactive sites on the catalyst intact to produce nanotubes.

[0130] Examples of gases that can be used as a diluent include argon or other inert gases, hydrogen, nitrogen, ammonia, carbon dioxide, and helium. Among these, hydrogen is particularly preferred as a gas that can be used as a diluent. The flow rate of the gas as a diluent is preferably 2000 mL (milliliters) / min or less, and more preferably 400 mL / min to 800 mL / min.

[0131] The gas pressure of the gaseous reactants and any diluents is preferably between 0.1 bar and 50 bar, more preferably between 0.5 bar and 5 bar, and even more preferably between 1 bar and 2 bar. In case of gas effluent from the furnace, the effluent gas can be recycled with or without cleaning.

[0132] The composition of the product particles can be controlled by monitoring the agglomerates and changing the reaction conditions based on the information obtained. For example, the agglomerates can be monitored by online Raman spectroscopy, which provides data indicative of single-walled or multi-walled CNTs. It also provides data indicative of the diameter and crystallinity of the CNTs. The agglomerates can also be monitored by online conductivity measurements, gas analysis, measuring the opacity of the reaction zone and / or measuring the winding force.

[0133] When the agglomerates are removed from the reactor, it is preferable to prevent air from entering the reactor, which is particularly important when the diluent gas contains hydrogen, for example to prevent an explosive mixture of hydrogen and air from forming in the reactor.

[0134] The product particles in production method X contain the MWCNTs of the present disclosure. Depending on the production conditions, in addition to the MWCNTs of the present disclosure, MWCNTs and / or SWCNTs other than the MWCNTs of the present disclosure may also be contained.

[0135] The product particles may be produced by chemical vapor deposition, where a gaseous reactant, a carbon source, is reacted in the presence of a catalyst.

[0136] Carbon-containing compounds suitable as carbon sources include, for example, carbon monoxide, carbon dioxide, aromatic hydrocarbons (e.g., benzene, toluene, xylene, cumene, ethylbenzene, naphthalene, or mesitylene), non-aromatic hydrocarbons (e.g., methane, ethane, propane, butane, pentane, hexane, cyclohexane, ethylene, propylene, or acetylene), and oxygen-containing hydrocarbons (e.g., formaldehyde, acetaldehyde, acetone, methanol, ethanol, diethyl ether, polyethylene glycol, 1-propanol, ethyl formate, and hydrocarbons including mixtures of two or more thereof). The carbon-containing compound is preferably carbon monoxide, methane, ethylene or acetylene.

[0137] The carbon source preferably contains oxygen. Ethanol is a particularly preferred carbon source. Oxygen can be introduced into the reactor by other methods, such as by using a diluent gas or a carbon source containing water.

[0138] The gaseous reactant that is the carbon source is preferably injected into the reactor at a rate of 0.01 mL / min to 10 mL / min, more preferably 0.08 mL / min to 0.25 mL / min.

[0139] The catalyst is preferably a transition metal group, in particular chromium (Cr), molybdenum (Mo), tungsten (W) or VIIIB transition metal group. Specifically, the catalyst is preferably, for example, iron (Fe), cobalt (Co), nickel (Ni), ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir) and platinum (Pt) or manganese (Mn), or a mixture thereof. Metals from the lanthanide and actinide series (e.g. yttrium (Y)) can also be used as catalyst. Fe, Ni, Co, Mo and mixtures thereof, for example, a mixture of Ni and Co (mass ratio: 50 / 50), a mixture of Fe and Ni, or a mixture of Fe and Mo are more preferred. Any of these transition metals may be used alone or in combination with any of the other transition metals listed to act as a catalyst for CNT growth, with it being particularly preferred that the catalyst is a mixture of two or more of the metals listed.

[0140] The catalyst is preferably formed by decomposition of a precursor. The precursor is preferably a thermally, photo- or plasma-decomposable compound of one or more of the above metals, such as a carbonyl or cyclopentadienyl organometallic compound. Ferrocene, iron pentacarbonyl, nickelocene and cobaltocene are particularly preferred precursors. Suitably, at least 0.01% by weight of the precursor is contained in the carbon source, and preferably 0.2% to 2.5% by weight of the precursor is contained in the carbon source. In one embodiment, 0.23% to 2.3% by weight of the precursor is contained in the carbon source. The catalyst may be used supported on a carrier, and preferred carriers include silica and magnesium oxide.

[0141] The carbon source is preferably reacted in the presence of a promoter. Suitable promoters are one or more of sulfur, phosphorus, molybdenum and organic compounds of these elements. Thiophene is also one of the preferred promoters. Suitably, up to 10% by weight (10% by weight or less) of the promoter is included in the carbon source. Preferably, 0.2% to 6% by weight of the promoter is included in the carbon source. When high or low concentrations of thiophene are used as the promoter, MWCNTs are formed. For example, MWCNTs are well formed using ethanol containing 0 mass % or 1.5 mass % to 4.0 mass % thiophene and 1.0 mass % to 10.0 mass % (particularly 2.3 mass %) ferrocene, with an injection rate of 5.0 mL / hour to 30.0 mL / hour (particularly 7.5 mL / hour), a hydrogen flow rate of 400 mL / min to 800 mL / min, and a synthesis temperature of 1100°C to 1180°C.

[0142] According to the production method X, it is possible to obtain fibrous CNTs having a length of at least 500 μm, for example, at least 1 mm. Fibrous CNTs can be in the form of threads (so-called fibers), sheets, or the like. The length of the fibrous CNTs can be controlled, for example, by the winding capacity of a spindle used in producing the fibrous CNTs.

[0143] The manufacturing method X preferably includes a step of reacting a carbon source in a reaction zone of a reactor to generate CNTs, and a step of aggregating the CNTs into aggregates by applying a force to the CNTs. According to this manufacturing method, fibrous CNTs can be easily manufactured.

[0144] In another embodiment, the MWCNTs may be produced in a reaction zone by the methods described above, followed by condensation to form agglomerates of MWCNTs, and continuous withdrawal of the MWCNTs from near the reaction zone. In another embodiment, the method includes generating the MWCNTs in a reaction zone, continuously electrostatically attracting the MWCNTs from the reaction zone, and recovering the MWCNTs.

[0145] [Multi-walled carbon nanotube dispersion] The MWCNT dispersion according to the present disclosure contains the MWCNT aggregate according to the present disclosure described above and a dispersion medium. The MWCNT aggregate according to the present disclosure has excellent dispersibility in a dispersion medium such as water, and therefore can be suitably used in the state of a dispersion liquid.

[0146] <Multi-walled carbon nanotube aggregates> The MWCNT dispersion according to the present disclosure contains the MWCNT aggregate according to the present disclosure. Details of the MWCNT aggregate according to the present disclosure are as described above, and therefore will not be described here.

[0147] The content of the MWCNT aggregate according to the present disclosure in the MWCNT dispersion according to the present disclosure is not particularly limited and can be appropriately set depending on the purpose. The content of the MWCNT aggregate according to the present disclosure in the MWCNT dispersion according to the present disclosure is, for example, from the viewpoint of the conductive effect, preferably 0.01 mass % or more, more preferably 0.05 mass % or more, even more preferably 0.1 mass % or more, and particularly preferably 0.2 mass % or more, relative to the total mass of the MWCNT dispersion. Furthermore, the content of the MWCNT aggregates according to the present disclosure in the MWCNT dispersion according to the present disclosure is, for example, from the viewpoint of dispersibility, preferably 20 mass % or less, more preferably 15 mass % or less, even more preferably 10 mass % or less, and particularly preferably 5 mass % or less, relative to the total mass of the MWCNT dispersion. In an embodiment, the content of the MWCNT aggregate according to the present disclosure in the MWCNT dispersion according to the present disclosure may be 0.01 mass% to 20 mass%, 0.05 mass% to 15 mass%, 0.1 mass% to 10 mass%, or 0.2 mass% to 5 mass%, relative to the total mass of the MWCNT dispersion.

[0148] <Dispersion medium> The MWCNT dispersion according to the present disclosure includes a dispersion medium. The dispersion medium preferably contains water, and more preferably contains water as a main component. "Containing water as a main component" means that the proportion of water in the dispersion medium is more than 50% by mass. The proportion of water in the dispersion medium is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more, and may be, for example, 100% by mass. The water is not particularly limited, but is preferably distilled water, ion-exchanged water, pure water, or the like, which contains fewer impurities.

[0149] The dispersion medium may be a mixture of water and a hydrophilic solvent. Examples of hydrophilic solvents include carbonate compounds such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and butylene carbonate; ether compounds such as tetrahydrofuran; ketone compounds such as acetone; lower alcohol compounds such as methanol and ethanol; and acetonitrile. When the dispersion medium contains a hydrophilic solvent, the proportion of the hydrophilic solvent in the dispersion medium is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.

[0150] <Dispersant> The MWCNT dispersion according to the present disclosure may include a dispersant. When the MWCNT dispersion according to the present disclosure contains a dispersant, the dispersibility and dispersion stability of the MWCNT aggregate according to the present disclosure can be improved. The dispersant is not particularly limited, and examples thereof include various surfactants. Examples of the dispersant also include polymer compounds such as resins. The dispersant is preferably a surfactant. The surfactant may be an ionic surfactant or a nonionic surfactant, and is not particularly limited.

[0151] Examples of ionic surfactants include anionic surfactants, cationic surfactants, and amphoteric surfactants. Examples of the anionic surfactant include aromatic sulfonic acid surfactants such as alkylbenzene sulfonates (e.g., dodecylbenzene sulfonate) and dodecylphenyl ether sulfonate; ether sulfate surfactants; phosphate surfactants; and carboxylic acid surfactants. Examples of the cationic surfactant include alkylamine salts and quaternary ammonium salts. Examples of the amphoteric surfactant include alkyl betaine surfactants and amine oxide surfactants. As the ionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic ionic surfactant) is preferred, and aromatic sulfonic acid surfactants such as alkylbenzene sulfonate and dodecyl phenyl ether sulfonate are more preferred. Aromatic ionic surfactants tend to be excellent in dispersing ability, dispersion stabilizing ability, and concentration enhancement for MWCNT aggregates.

[0152] Examples of nonionic surfactants include sugar ester surfactants such as sorbitan fatty acid esters and polyoxyethylene sorbitan fatty acid esters; fatty acid ester surfactants such as polyoxyethylene resin acid esters and polyoxyethylene fatty acid diethyl esters; ether surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers and polyoxyethylene polypropylene glycols; and aromatic nonionic surfactants such as polyoxyalkylene octyl phenyl ether, polyoxyalkylene nonyl phenyl ether, polyoxyalkyl dibutyl phenyl ether, polyoxyalkyl styryl phenyl ether, polyoxyalkyl benzyl phenyl ether, polyoxyalkyl bisphenyl ether, polyoxyalkyl cumyl phenyl ether and polyoxyalkylene phenyl ether. As the nonionic surfactant, an ionic surfactant having an aromatic ring (so-called aromatic nonionic surfactant) is preferable, polyoxyalkylene phenyl ether is more preferable, and polyoxyethylene phenyl ether is further preferable. Aromatic nonionic surfactants tend to be excellent in dispersing ability, dispersion stabilizing ability, and concentration enhancement for MWCNT aggregates.

[0153] Other dispersants that are excellent in dispersibility, dispersion stability, and high concentration of MWCNT aggregates include β-naphthalenesulfonic acid formalin condensate sodium salts, such as Demol N, Demol RN, and Demol T (manufactured by Kao Corporation), polyoxyethylene stearyl ether Brij S 100 (manufactured by Sigma-Aldrich), polyvinylpyrrolidone K30 (manufactured by, for example, Fujifilm Wako Pure Chemical Industries, Ltd.), carboxymethylcellulose (CMC) (manufactured by, for example, Daicel Miraize Co., Ltd.), sodium deoxycholate (manufactured by, for example, Fujifilm Wako Pure Chemical Industries, Ltd.), and SOLSPERSE TM W100, SOLSPERSE TM W150 (manufactured by Lubrizol Japan, Ltd.) CMC is particularly preferred from the viewpoint of excellent dispersibility, dispersion stabilization ability, and high concentration of MWCNT aggregates.

[0154] When the MWCNT dispersion according to the present disclosure contains a dispersant, it may contain only one type of dispersant, or may contain two or more types of dispersants.

[0155] When the MWCNT dispersion according to the present disclosure contains a dispersant, the content of the dispersant in the MWCNT dispersion is not particularly limited and can be set appropriately depending on the type of dispersant, the amount of MWCNT aggregates, the amount of dispersion medium, etc. An example of the content of the dispersant in the MWCNT dispersion according to the present disclosure is 0.01% by mass to 20% by mass relative to the total mass of the MWCNT dispersion.

[0156] <Other ingredients> The MWCNT dispersion according to the present disclosure may contain components (so-called other components) other than the MWCNT aggregates and dispersion medium according to the present disclosure, as long as the effects of the dispersion are not impaired. Examples of the other components include various additives such as antifoaming agents and antistatic agents. Examples of the other components include CNTs other than the MWCNTs of the present disclosure and carbon materials other than CNTs. The MWCNT dispersion according to the present disclosure may contain trace amounts of impurity components (for example, unavoidable impurities) as long as the effects of the dispersion are not impaired.

[0157] <<Applications of multi-walled carbon nanotube dispersion liquid>> The use of the MWCNT dispersion according to the present disclosure is not particularly limited. The MWCNT dispersion according to the present disclosure has excellent dispersibility of MWCNT aggregates and high conductivity, and therefore can be applied to, for example, conductive materials such as conductive inks, antistatic agents, conductive materials for forming circuit patterns, materials for transparent electrodes, and water-soluble polymer fillers. The MWCNT dispersion according to the present disclosure can be suitably used, for example, as a conductive ink for forming electrodes (particularly, negative electrodes) of various secondary batteries such as lithium ion batteries. By using the MWCNT dispersion according to the present disclosure as a conductive ink, electrodes with high conductivity can be easily manufactured.

[0158] [Method of manufacturing multi-walled carbon nanotube dispersion liquid] The method for producing the MWCNT dispersion according to the present disclosure is not particularly limited. The MWCNT dispersion according to the present disclosure can be produced by dispersing the MWCNT aggregate according to the present disclosure in a dispersion medium. That is, the MWCNT dispersion according to the present disclosure can be produced by a method including a step of dispersing the MWCNT aggregate according to the present disclosure in a dispersion medium (also referred to as a "dispersion step").

[0159] <Dispersion process> The dispersion step is a step of dispersing the MWCNT aggregate according to the present disclosure in a dispersion medium. In the dispersion step, a dispersant may be used from the viewpoint of improving the dispersibility and dispersion stability of the MWCNT aggregate according to the present disclosure. The details of the MWCNT aggregate, the dispersion medium, and the dispersant according to the present disclosure are as described above, and therefore will not be described here.

[0160] The dispersion method is not particularly limited. Examples of the dispersion method include methods using a dispersion device such as a stirrer, homogenizer, colloid mill, flow jet mixer, dissolver, paint conditioner, Manton emulsifier, jet mill, and ultrasonic device (e.g., ultrasonic disperser). Examples of the dispersion method include methods using known pulverization means, such as ball milling (e.g., ball mill, vibration ball mill, planetary ball mill, bead mill, etc.), sand milling, colloid milling, jet milling, roller milling, and dispersing machines such as vertical or horizontal agitator mills, attritors, colloid mills, three-roll mills, pearl mills, super mills, impellers, dispersers, KD mills, dynatrons, and pressure kneaders. As a dispersion method, a method using a jet mill is preferable, and a method using a wet jet mill is more preferable. A wet jet mill is a dispersion device that pressure-feeds a mixture in a solvent as a high-speed flow from a nozzle arranged in a sealed pressure-resistant container. In the wet jet mill, the aggregates of multi-walled carbon nanotubes are dispersed by collisions between opposing flows in a pressure-resistant container, collisions with the container wall, turbulence caused by the high-speed flow, shear flow, and the like. As the wet jet mill, an ultra-high pressure homogenizer (model number: NAGS20, NAGS100, NAGS200, NAGS1000, etc.) manufactured by Jokou Co., Ltd. can be suitably used. However, the wet jet mill is not limited to this. When the above-mentioned ultra-high pressure homogenizer is used as the dispersing device, the dispersion treatment pressure is preferably 10 MPa to 250 MPa.

[0161] <Drying process> The method for producing the MWCNT dispersion according to the present disclosure may include a step of drying the MWCNT aggregate according to the present disclosure (also referred to as a "drying step") prior to the above-mentioned dispersion step. When moisture adheres to MWCNTs, the MWCNTs tend to stick together due to the surface tension of the water. By performing a drying process before the dispersion process, the moisture adhering to the MWCNTs is removed and the adhesion of the MWCNTs to each other due to moisture adhesion is suppressed, thereby further improving the dispersibility of the MWCNT aggregates. The drying method is not particularly limited. Examples of the drying method include heat drying, vacuum drying, and heat vacuum drying. The drying method is preferably heated vacuum drying. The drying temperature is not particularly limited, and is preferably from 40°C to 100°C, for example. The drying time is not particularly limited and can be appropriately set depending on the drying temperature, the degree of moisture adhering to the MWCNTs, and the like.

[0162] The MWCNT dispersion according to the present disclosure can be suitably produced, for example, by the method described in the examples below.

[0163] [Conductive materials] The conductive material according to the present disclosure includes the MWCNT aggregate according to the present disclosure. As described above, the MWCNT aggregate according to the present disclosure contained in the conductive material according to the present disclosure has high conductivity and excellent dispersibility when made into a dispersion, and is therefore suitable as a conductive auxiliary. Since the conductive material according to the present disclosure contains the MWCNT aggregate according to the present disclosure, it has excellent conductive efficiency and can effectively impart high conductivity to an object of use.

[0164] The conductive material according to the present disclosure may contain a known conductive assistant such as graphite, Ketjen black, etc. Furthermore, the conductive material according to the present disclosure may contain CNTs other than the MWCNT aggregate according to the present disclosure.

[0165] The conductive material according to the present disclosure can be used as one of electrode materials. An example of an electrode formed using the electrode material is an electrode included in a secondary battery. Hereinafter, an embodiment of the electrode and the secondary battery including the electrode will be described.

[0166] <Electrode> The electrodes may include the MWCNT aggregates according to the present disclosure described above. In an electrode, the MWCNT aggregate according to the present disclosure can function as a conductive assistant. The MWCNT aggregate contained in the electrode described below is synonymous with the MWCNT aggregate according to the present disclosure, and preferred embodiments are also the same, so description of the MWCNT aggregate will be omitted below.

[0167] The electrode may be at least one of a positive electrode and a negative electrode. The electrode may include an electrode active material layer, or may include a current collector and an electrode active material layer disposed on the current collector.

[0168] There are no particular limitations on the current collector, so long as it does not induce a chemical change in the battery and has electrical conductivity. The current collector may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. Specifically, a transition metal such as copper or nickel that has good carbon adsorption properties may be used as the current collector.

[0169] The electrode active material layer can include an electrode active material. The electrode active material is preferably electrode active material particles. When the electrode is a positive electrode, the electrode active material is not particularly limited, and the electrode active material layer can contain a positive electrode active material that is commonly used as an electrode material for a positive electrode. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7; chemical formula LiNi 1-c2 M c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.66); 2-c3 M c3 Examples of such oxides include lithium manganese composite oxides represented by the formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is substituted with an alkaline earth metal ion.

[0170] When the electrode is a negative electrode, the electrode active material is not particularly limited, and the electrode active material layer can include a negative electrode active material commonly used for negative electrode materials. Specifically, the negative electrode active material can include graphite-based active material particles or silicon-based active material particles. As the graphite-based active material particles, at least one selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fibers, and graphitized mesocarbon microbeads may be used. By using artificial graphite as the graphite-based active material particles, the rate characteristics can be improved. As the silicon-based active material particles, at least one selected from the group consisting of Si, SiOx (0 < x < 2), Si-C composites, and Si-Y alloys (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, Group 13 elements, Group 14 elements, rare earth elements, and combinations thereof) may be used. By using silicon-based active material particles, the battery can be made to have a higher capacity.

[0171] The electrode active material layer can further include a binder. The binder is not particularly limited, and the electrode active material layer can include a binder commonly used for electrode materials. Examples of the binder include at least one polymer selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and polyacrylic acid, and polymers in which hydrogen atoms of these polymers are substituted with Li, Na, Ca, etc.

[0172] <Secondary battery> The secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. At least one of the positive electrode and the negative electrode is an electrode formed using an electrode material including the MWCNT aggregate according to the present disclosure.

[0173] The separator separates the negative electrode and the positive electrode and provides a path for lithium ion migration, and is not particularly limited as long as it is a separator that is usually used as a separator in a secondary battery. The separator preferably has low resistance to ion migration of the electrolyte and is excellent in the ability to wet the electrolyte solution. A specific example of the separator is a porous polymer film. The porous polymer film may be, for example, a porous polymer film made from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure in which two or more of these films are laminated. The separator may be a typical porous nonwoven fabric, for example, a nonwoven fabric made of high-melting-point glass fiber, polyethylene terephthalate fiber, etc. The separator may be coated with a ceramic component or a polymeric substance to ensure heat resistance or mechanical strength. The separator may optionally be of single layer or multi-layer construction.

[0174] The electrolyte is not particularly limited, and examples thereof include electrolytes such as organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used when manufacturing lithium secondary batteries.

[0175] Specifically, the electrolyte can include a non-aqueous organic solvent and a metal salt. Examples of non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0176] Among carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are preferably used as non-aqueous organic solvents because they have a high dielectric constant as a high-viscosity organic solvent and dissociate lithium salts well. It is more preferable to use such a cyclic carbonate mixed with a linear carbonate having a low viscosity and a low dielectric constant such as dimethyl carbonate or diethyl carbonate in an appropriate ratio as a non-aqueous organic solvent, since an electrolyte having a high electrical conductivity can be obtained.

[0177] The metal salt may be a lithium salt. The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. The anion portion of the lithium salt is, for example, F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3- , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - Examples include:

[0178] In addition to the non-aqueous organic solvent and metal salt, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0179] The above-mentioned secondary battery can be configured into a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack can be used as a power source for a medium to large device selected from the group consisting of, for example, an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0180] [Planar aggregate] The planar aggregate according to the present disclosure includes the MWCNT aggregate according to the present disclosure. The ratio of the MWCNT aggregate according to the present disclosure contained in the planar aggregate according to the present disclosure is usually 1 mass % or more with respect to the total mass of the planar aggregate. The planar aggregate according to the present disclosure may contain other components such as CNT aggregates (particularly MWCNT aggregates) having a maximum length of less than 1000 μm.

[0181] [Method for producing planar assemblies] The method for producing the planar assembly according to the present disclosure is not particularly limited. The planar aggregate according to the present disclosure can be produced, for example, as a nonwoven fabric-like planar aggregate, by dispersing the MWCNT aggregate according to the present disclosure, or the MWCNT aggregate according to the present disclosure and other components, such as a CNT aggregate (particularly an MWCNT aggregate) having a maximum length of less than 1000 μm, in water or other fluid, and filtering once or twice or more times.

[0182] An example of the planar assembly according to the present disclosure is a film.

[0183] Planar assemblies according to the present disclosure are useful, for example, in filters, electromagnetic shields, and extreme ultraviolet (EUV) pellicles. EXAMPLES

[0184] The MWCNT aggregate according to the present disclosure will be described in more detail below with reference to examples. The MWCNT aggregate according to the present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.

[0185] [Production of MWCNT aggregates or preparation of SWCNT aggregates] <Example 1> The MWCNT aggregate 1 in Example 1 was produced by a floating catalyst method (CVD method) that directly interacts with the self-assembly of CNT bundles in the gas phase. First, ferrocene as a metal catalyst precursor containing Fe atoms and thiophene as a promoter were introduced into a continuous flow of carrier gas in a once-through reactor whose temperature was controlled at 400° C. to 700° C. A mixture of nitrogen and argon gas was used as the carrier gas, and the flow rate of the carrier gas was 30,000 sccm (standard cubic centimeter per minute). By maintaining the temperature in the flow-through reactor within the above range, the metal catalyst precursor was produced as a particulate metal catalyst. The region in which the metal catalyst was produced is referred to as the first temperature zone. The carbon source, methane, was then released into the carrier gas stream. The metal catalyst and carbon source were fed into a second temperature zone downstream of the first temperature zone, which was temperature-controlled at 1400° C. The second temperature zone was maintained at a temperature sufficient to produce carbon nanotube aggregates. In the second temperature zone, an electric field was generated in a temperature-controlled flow reactor, which generated MWCNT aggregates. The generated aggregates were continuously discharged through the outlet of a flow-type reactor whose temperature was controlled at 100°C to 500°C, and collected as sheet-like MWCNT aggregates by continuous discharge. The collected sheet-like MWCNT aggregates were immersed in a PTFE tray containing hydrochloric acid (special grade reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) for 24 hours. After that, the MWCNT aggregates were removed from the tray and washed with deionized water until the pH of the washing water reached 7. In this manner, the MWCNT aggregate 1 of Example 1 was obtained.

[0186] <Example 2> MWCNT aggregate 2 of Example 2 was obtained in accordance with Example 1, except that the sheet-like MWCNT aggregate collected in Example 1 was washed with deionized water for 10 seconds.

[0187] <Example 3> The MWCNT aggregate 3 in Example 3 was prepared by a floating catalyst method (CVD method) that directly interacts with the self-assembly of CNT bundles in the gas phase, similar to the sheet-like MWCNT aggregate collected in Example 1. First, ferrocene as a metal catalyst precursor containing Fe atoms and thiophene as a promoter were introduced into a continuous flow of carrier gas in a once-through reactor whose temperature was controlled at 400°C to 700°C. A mixture of nitrogen and argon was used as the carrier gas. The flow rate of the carrier gas was 30,000sccm. By maintaining the temperature in the flow-through reactor within the above range, the metal catalyst precursor was produced as a particulate metal catalyst. The region in which the metal catalyst was produced is referred to as the first temperature zone. The carbon source, methane, was then released into the carrier gas stream. The metal catalyst and carbon source were fed into a second temperature zone downstream of the first temperature zone, which was temperature-controlled at 1400° C. The second temperature zone was maintained at a temperature sufficient to produce carbon nanotube aggregates. In the second temperature zone, an electric field was generated in a temperature-controlled flow reactor, which generated MWCNT aggregates. The generated aggregates were continuously discharged through the outlet of a flow-type reactor whose temperature was controlled at 100°C to 500°C, and collected as fibrous MWCNT aggregates by continuous discharge. The collected fibrous MWCNT aggregates were washed with deionized water for 10 s. In this manner, MWCNT aggregate 3 of Example 3 was obtained.

[0188] <Comparative Example 1> SWCNT aggregate 1 [Product name: TUBALL TM , single-walled carbon nanotube powder, manufactured by OCSiAl Corporation] was used as Comparative Example 1.

[0189] <Comparative Example 2> MWCNT aggregate 4 [product number: 901019, multi-walled carbon nanotube powder, manufactured by Sigma-Aldrich] was used as Comparative Example 2.

[0190] <Comparative Example 3> MWCNT aggregate 5 (product number: FT7000, multi-walled carbon nanotube powder, manufactured by C-nano Corporation) was used as Comparative Example 3.

[0191] [evaluation] The following evaluations were performed on MWCNT aggregate 1 of Example 1, MWCNT aggregate 2 of Example 2, MWCNT aggregate 3 of Example 3, SWCNT aggregate 1 of Comparative Example 1, MWCNT aggregate 4 of Comparative Example 2, and MWCNT aggregate 5 of Comparative Example 3. Hereinafter, for convenience, "MWCNT aggregate 1 of Example 1, MWCNT aggregate 2 of Example 2, MWCNT aggregate 3 of Example 3, SWCNT aggregate 1 of Comparative Example 1, MWCNT aggregate 4 of Comparative Example 2, and MWCNT aggregate 5 of Comparative Example 3" may be collectively referred to as "CNT aggregate".

[0192] 1. Observation of SEM images (1) Preparation of CNT dispersion for SEM photography (1-1) MWCNT aggregate 1 of Example 1 1.1 g of the MWCNT aggregate 1 of Example 1, 1.65 g of carboxymethyl cellulose (trade name: Carboxymethyl Cellulose Sodium Salt High Viscosity, manufactured by MP Biomedicals) as a dispersant, and 547.25 g of ion-exchanged water were mixed. The resulting mixture was subjected to a dispersion treatment for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. as a pre-dispersion before the main dispersion, to obtain a dispersion A. Note that the MWCNT aggregate 1 was cut into small pieces of about 1 cm square using scissors before mixing so that the MWCNT aggregate 1 would not get tangled in the blades of the homogenizer. Next, the dispersion liquid A obtained above was subjected to a main dispersion treatment under the following conditions using an ultra-high pressure homogenizer (model: NAGS100) manufactured by Joko Corporation, which is a wet jet mill, to obtain CNT dispersion liquid A for SEM photography.

[0193] -conditions- Nozzle diameter: 0.22mm Pressure: 85MPa Number of times: 8 Method: Circulation method

[0194] (1-2) MWCNT aggregate 2 of Example 2 1.1 g of the MWCNT aggregate 2 of Example 2, 1.65 g of carboxymethyl cellulose (trade name: Carboxymethyl Cellulose Sodium Salt High Viscosity, manufactured by MP Biomedicals) as a dispersant, and 547.25 g of ion-exchanged water were mixed. The resulting mixture was subjected to a dispersion treatment for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. as a pre-dispersion before the main dispersion, to obtain a dispersion B. Note that the MWCNT aggregate 2 was cut into small pieces of about 1 cm square using scissors before mixing so that the MWCNT aggregate 2 would not get tangled in the blades of the homogenizer. Next, the dispersion liquid B obtained above was subjected to a main dispersion treatment under the same conditions as the main dispersion treatment in "(1-1) MWCNT aggregate 1 in Example 1" above, using an ultra-high pressure homogenizer [model number: NAGS100], which is a wet jet mill manufactured by Joko Corporation, to obtain a CNT dispersion liquid B for SEM photography.

[0195] (1-3) MWCNT aggregate 3 of Example 3 1.1 g of the MWCNT aggregate 3 of Example 3, 1.65 g of carboxymethyl cellulose (trade name: Carboxymethyl Cellulose Sodium Salt High Viscosity, manufactured by MP Biomedicals) as a dispersant, and 547.25 g of ion-exchanged water were mixed. The resulting mixture was subjected to a dispersion treatment for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. as a pre-dispersion before the main dispersion, to obtain a dispersion C. Note that the MWCNT aggregate 3 was cut to a length of about 1 cm using scissors before mixing so that the MWCNT aggregate 3 would not get tangled in the blades of the homogenizer. Next, the dispersion liquid C obtained above was subjected to a main dispersion treatment under the same conditions as the main dispersion treatment in "(1-1) MWCNT aggregate 1 in Example 1" above, using an ultra-high pressure homogenizer (model number: NAGS100) manufactured by Joko Corporation, which is a wet jet mill, to obtain a CNT dispersion liquid C for SEM photography.

[0196] (1-4) SWCNT aggregate 1 of Comparative Example 1 As the dispersion liquid of SWCNT aggregate 1 of Comparative Example 1, CNT dispersion liquid D for SEM photography [product name: TUBALL TM BATT H2O, single-walled carbon nanotube aqueous solution, manufactured by OCSiAl Corporation] was used. The CNT concentration was adjusted to 0.2 mass%.

[0197] (1-5) MWCNT aggregate 4 of Comparative Example 2 1.1 g of MWCNT aggregate 4 of Comparative Example 2, 1.65 g of carboxymethyl cellulose (trade name: Carboxymethyl Cellulose Sodium Salt High Viscosity, manufactured by MP Biomedicals) as a dispersant, and 547.25 g of ion-exchanged water were mixed. The obtained mixture was subjected to a dispersion treatment for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. as a pre-dispersion before the main dispersion, to obtain a dispersion E. Next, the dispersion liquid E obtained above was subjected to a main dispersion treatment under the same conditions as the main dispersion treatment in "(1-1) MWCNT aggregate 1 in Example 1" above, using an ultra-high pressure homogenizer [model number: NAGS100], which is a wet jet mill manufactured by Joko Corporation, to obtain a CNT dispersion liquid E for SEM photography.

[0198] (1-6) MWCNT aggregate 5 of Comparative Example 3 1.1 g of the MWCNT aggregate 5 of Comparative Example 3, 1.65 g of carboxymethyl cellulose (trade name: Carboxymethyl Cellulose Sodium Salt High Viscosity, manufactured by MP Biomedicals) as a dispersant, and 547.25 g of ion-exchanged water were mixed. The resulting mixture was subjected to a dispersion treatment for 1 hour using an Ace Homogenizer manufactured by Nippon Seiki Co., Ltd. as a pre-dispersion before the main dispersion, thereby obtaining a dispersion F. Next, the dispersion liquid F obtained above was subjected to a main dispersion treatment under the same conditions as the main dispersion treatment in "(1-1) MWCNT aggregate 1 in Example 1" above, using an ultra-high pressure homogenizer [model number: NAGS100], which is a wet jet mill manufactured by Joko Corporation, to obtain a CNT dispersion liquid F for SEM photography.

[0199] (2) Taking SEM images (2-1) MWCNT aggregate 1 of Example 1 When an SEM photograph (magnification: 5000 times) of the MWCNT aggregate 1 of Example 1 was taken, it was confirmed that a plurality of MWCNTs with maximum lengths in the range of 500 μm to 30000 μm were present within the viewing angle of the SEM photograph. In addition, multiple SEM photographs (magnification: 5000x) were taken of the MWCNT aggregate 1 of Example 1 at adjacent viewing angles, and focusing on 100 MWCNTs included in the viewing angle of the SEM photographs, the maximum length of each was measured. Of the observed MWCNTs, the proportion of MWCNTs with maximum lengths in the range of 500 μm to 30,000 μm (i.e., SLMWCNTs) was 90%, and the maximum value of the maximum length of the observed 100 MWCNTs was 3500 μm.

[0200] (2-2) MWCNT aggregate 2 of Example 2 When an SEM photograph (magnification: 5000 times) of the MWCNT aggregate 2 of Example 2 was taken, it was confirmed that a plurality of MWCNTs with maximum lengths in the range of 500 μm to 30000 μm were present within the viewing angle of the SEM photograph. In addition, multiple SEM photographs (magnification: 5000x) were taken of the MWCNT aggregate 2 of Example 2 at adjacent viewing angles, and focusing on 100 MWCNTs included in the viewing angle of the SEM photographs, the maximum length of each was measured. Of the observed MWCNTs, the proportion of MWCNTs with maximum lengths in the range of 500 μm to 30,000 μm (i.e., SLMWCNTs) was 90%, and the maximum value of the maximum length of the observed 100 MWCNTs was 3500 μm.

[0201] (2-3) MWCNT aggregate 3 of Example 3 When an SEM photograph (magnification: 5000 times) of the MWCNT aggregate 3 of Example 3 was taken, it was confirmed that within the viewing angle of the SEM photograph, there were multiple MWCNTs with maximum lengths in the range of 500 μm to 30000 μm. In addition, multiple SEM photographs (magnification: 5000x) were taken of the MWCNT aggregate 3 of Example 3 at adjacent viewing angles, and focusing on 100 MWCNTs included in the viewing angle of the SEM photographs, the maximum length of each was measured. Of the observed MWCNTs, the proportion of MWCNTs with maximum lengths in the range of 500 μm to 30,000 μm (i.e., SLMWCNTs) was 90%, and the maximum value of the maximum length of the 100 observed MWCNTs was 4000 μm.

[0202] (2-4) CNT dispersion A, CNT dispersion D, and CNT dispersion E SEM photographs of the CNT dispersion A for SEM photography, CNT dispersion D, and CNT dispersion E prepared above were taken at a magnification of 500 times using a scanning electron microscope. The results are shown in Figures 1A, 1B and 1C.

[0203] FIG. 1A is an SEM photograph of CNT dispersion A for SEM photography containing MWCNT aggregate 1 of Example 1, FIG. 1B is an SEM photograph of CNT dispersion D for SEM photography containing SWCNT aggregate 1 of Comparative Example 1, and FIG. 1C is an SEM photograph of CNT dispersion E for SEM photography containing MWCNT aggregate 4 of Comparative Example 2. As shown in Fig. 1A, it was confirmed that a plurality of fibrous MWCNTs were entangled to form aggregates in CNT dispersion A for SEM photography containing MWCNT aggregate 1 of Example 1. On the other hand, as shown in Fig. 1B and Fig. 1C, almost no entanglement of CNTs was confirmed in CNT dispersion D for SEM photography containing SWCNT aggregate 1 of Comparative Example 1 and CNT dispersion E for SEM photography containing MWCNT aggregate 4 of Comparative Example 2.

[0204] 2. Median diameter The median diameter of the CNTs contained in the CNT aggregate was measured. The CNT dispersions A to F for SEM photography obtained in "(1) Preparation of CNT dispersions for SEM photography" in "1. Observation of SEM photographs" above were diluted with ion-exchanged water to obtain aqueous dispersions A to F with CNT concentrations of 0.004 mass%. The resulting aqueous dispersions A to F were used as measurement samples, and the volumetric particle size distribution of the CNTs was measured under the following measurement conditions using a centrifugal sedimentation type dispersion stability particle size distribution analyzer LUMiSizer 611 (product name) manufactured by LUM GmbH as the measurement device. In the measured volumetric particle size distribution, the particle size at which the cumulative frequency was 50% was read and taken as the median size. The results are shown in Table 1.

[0205] <Measurement conditions> Measurement cell: Polycarbonate cell (optical path length: 2 mm) Rotational speed: 4000 rpm Centrifugal acceleration: 2300×g Measurement interval: 30 seconds Number of measurements: 1000 Measurement temperature: 25℃

[0206] 3. Rate of change of transmittance The rate of change in transmittance of the CNTs contained in the CNT aggregate was measured. The CNT dispersions A to F for SEM photography (CNT concentration: 0.2 mass%) obtained in "(1) Preparation of CNT dispersion for SEM photography" in "1. Observation of SEM photographs" above were used as measurement samples, and a centrifugal sedimentation type dispersion stability particle size distribution device LUMiSizer 611 (product name) manufactured by LUM GmbH was used as the measurement device to obtain a sedimentation profile under the following measurement and analysis conditions. The rate of change in the overall transmittance was analyzed from the obtained sedimentation profile to determine the rate of change in the transmittance. The results are shown in Table 1.

[0207] <Measurement / analysis conditions> Measurement cell: Polycarbonate cell (optical path length: 2 mm) Rotational speed: 4000 rpm Centrifugal acceleration: 2300×g Measurement interval: 30 seconds Number of measurements: 1000 Dispersion medium viscosity: 0.8946 mPa s Density of dispersion medium: 997.3kg / m 3 Density of dispersoid: 1350kg / m3 Refractive index of dispersion medium (real part): 1.326 Refractive index of dispersoid (real part): 1.630 Refractive index of dispersion medium (imaginary part): 0.5153 Under the above analysis conditions, the dispersion medium is water and the dispersoid is CNT. The above viscosity, density and refractive index values ​​are all values ​​at 25°C.

[0208] 4. Scattering intensity ratio S1 / S2 and scattering intensity ratio S3 / S4 The scattering intensity ratios S1 / S2 and S3 / S4 of the CNTs contained in the CNT aggregate were measured. The CNT dispersions A to F (CNT concentration: 0.2 mass %) for SEM photography obtained in "(1) Preparation of CNT dispersion for SEM photography" in "1. Observation of SEM photographs" above were used as measurement samples. The measurement sample was packed into an NMR tube (product name: S-3-HT-7, manufactured by NORELL) with an outer diameter of 2.99±0.03 mm and an inner diameter of 2.41±0.03 mm, taking care not to introduce bubbles, and then the scattering profile of the CNT was obtained using the beamline BL03XU of SPring-8, a large-scale synchrotron radiation facility, as the small-angle X-ray scattering experimental equipment. Measurements using the small-angle X-ray scattering method were performed according to the description in "Structural Science of Crystalline Polymers, Kohji Tashiro, Springer, 2022". More specifically, measurements were performed under conditions of an X-ray wavelength of 0.1 nm, a beam diameter of 100 μm, and a camera length of 8000 mm, using a Pilatus1M detector manufactured by Dectris, and an ambient temperature of 25 ° C. In the measurement, no attenuator was used, and X-rays were incident in a direction perpendicular to the length direction near the axial center of the NMR tube. The exposure time was 1 second, and the irradiation position was changed by 100 μm in the length direction for 10 measurements, to obtain a total two-dimensional scattering image Ms. In addition, the transmitted light intensity fs was measured in the ion chamber downstream of the NMR tube at the same time as the two-dimensional scattering image was taken. The background two-dimensional scattering image Mb and transmitted light intensity fb were measured under the same conditions as above, except that the NMR tube was filled with ion-exchanged water instead of the aqueous dispersion. A two-dimensional scattering image M after background correction was obtained using the following formula (1). At this time, the area in which the scattered X-rays were blocked by a beam stopper or the like installed to prevent the direct beam from entering the detector was excluded from the two-dimensional scattering image M. M = Ms / fs-Mb / fb (1) A one-dimensional radial profile was obtained by circular averaging from the two-dimensional scattering image M. The horizontal axis was calibrated to the magnitude q of the scattering vector using collagen, a standard material. From the obtained one-dimensional profile, the magnitude of the scattering vector q = 0.2 nm -1 Scattering intensity S1 at q = 0.8 nm -1 Scattering intensity S2 at q = 0.02 nm -1 Scattering intensity S3 and the magnitude of the scattering vector q at 0.08 nm -1 The scattering intensity S4 at this point was read, and the scattering intensity ratio S1 / S2 and the scattering intensity ratio S3 / S4 were calculated. The results are shown in Table 2. The scattering profile of each CNT aggregate obtained by small-angle X-ray scattering is shown in Figure 2.

[0209] 5. Conductivity The CNT dispersions A to F for SEM photography (CNT concentration: 0.2 mass%) obtained in "(1) Preparation of CNT dispersion for SEM photography" in "1. Observation of SEM photography" above were dropped onto a glass substrate cut to a size of 10 cm x 10 cm, and a film was formed using a stainless steel applicator with a gap size of 150 μm. Thereafter, the glass substrate was heated on a hot plate at 110°C for 10 minutes, the film was dried, and CNT assembly films A to F were obtained. The surface resistivity of the CNT assembly films A to F thus obtained was measured using a resistivity meter Loresta GXII (product name) manufactured by Nitto Seiko Analytech Co., Ltd. The surface resistivity was measured at five different points of the CNT assembly film, and the average value was taken as the surface resistivity of the CNT assembly. In addition, based on the surface resistivity of the CNT assembly, the conductivity of the CNT assembly was evaluated according to the following evaluation criteria. The results are shown in Tables 1 and 2. If the evaluation result was "A" or "B", it was determined that the electrical conductivity was excellent. An evaluation result of "A" is most preferable.

[0210] -Evaluation criteria- A: The surface resistivity of the CNT aggregate is 1.00×10 2 It is less than Ω / sq. B: The surface resistivity of the CNT aggregate is 1.00×10 2 Ω / sq or more 3.00×10 2 It is in the range of less than Ω / sq. C: The surface resistivity of the CNT aggregate is 3.00×10 2 Ω / sq or more 1.00×10 5 It is in the range of less than Ω / sq. D: The surface resistivity of the CNT aggregate is 1.00×10 5 More than Ω / sq.

[0211] 6. Peak intensity ratio G1 / D1 in Raman spectrum The Raman spectrum of the CNTs contained in the CNT aggregate was measured. The CNT aggregate was fixed on a sample stage, and a Raman spectrum was obtained under the following measurement conditions using a Raman spectrometer, RAMAN-11 (product name), manufactured by Nanophoton Corporation.

[0212] <Measurement conditions> Excitation laser wavelength: 532 nm Grating: 600 grooves / mm Objective lens: 20x, numerical aperture (NA) 0.45 Wavelength range: 110cm -1 ~2650cm -1

[0213] 1550cm -1 ~1600cm -1 The maximum scattering intensity at the Raman shift of 1300 cm is defined as the G band peak intensity G1 in the Raman spectrum. -1 ~1400cm -1The maximum value of the scattering intensity at the Raman shift of was taken as the peak intensity D1 of the D band in the Raman spectrum, and the peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum, was calculated from each value. The results are shown in Table 3.

[0214] 7.BET specific surface area The BET specific surface area of ​​the CNTs contained in the CNT aggregate was measured. The BET specific surface area of ​​the CNTs was determined by a gas adsorption method using nitrogen gas in accordance with JIS Z 8830: 2013. Specifically, it was determined by the following method. First, the CNT aggregate was packed into a sample tube, and the inside of the sample tube was evacuated to a vacuum at 300°C for 3 hours using a pretreatment device, BELPREP-vacII (product name), manufactured by Microtrack-Bell Corporation, to pretreat the CNT aggregate. The pretreated CNT aggregate was used as a measurement sample, and the nitrogen adsorption amount of the CNT aggregate was measured under the following measurement conditions using a specific surface area measuring device, BELSORP-mini II (product name), manufactured by Microtrack-Bell, Inc., to obtain an adsorption / desorption isotherm. The BET specific surface area was calculated from the obtained adsorption / desorption isotherm under the following analysis conditions. The results are shown in Table 3.

[0215] <Measurement / analysis conditions> Measurement method: constant volume method Adsorption temperature: 77K Adsorbate: Nitrogen Saturated vapor pressure: Actual measurement Equilibration time: 500 sec Specific surface area: BET method (BET-Plot)

[0216] [Table 1]

[0217] As shown in Table 1, MWCNT aggregate 1 of Example 1, MWCNT aggregate 2 of Example 2, and MWCNT aggregate 3 of Example 3, which contain MWCNTs having a median diameter of 80 nm or more in the volume-based particle size distribution obtained by centrifugal sedimentation when made into an aqueous dispersion at a concentration of 0.004 mass%, and having a rate of change in transmittance measured by centrifugal sedimentation of 0.3% / hour or less when made into an aqueous dispersion at a concentration of 0.2 mass%, were confirmed to have excellent electrical conductivity. On the other hand, it was confirmed that SWCNT aggregate 1 of Comparative Example 1, MWCNT aggregate 4 of Comparative Example 2, and MWCNT aggregate 5 of Comparative Example 3, which contain CNTs that do not satisfy at least one of the above median diameter being 80 nm or more and the above rate of change in transmittance being 0.3% / hour or less, have inferior electrical conductivity compared to the Examples.

[0218] [Table 2]

[0219] As shown in Table 2, when the aqueous dispersion was prepared at a concentration of 0.2 mass%, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering was q = 0.2 nm -1 Scattering intensity S1 and scattering vector magnitude q=0.8 nm -1 It was confirmed that MWCNT aggregate 1 of Example 1, MWCNT aggregate 2 of Example 2, and MWCNT aggregate 3 of Example 3, which contain MWCNTs having a scattering intensity ratio S1 / S2 of 90 or more, which is the ratio of the scattering intensity S1 to the scattering intensity S2 at 100 nm, have excellent electrical conductivity. -1 Scattering intensity S3 and scattering vector magnitude q at 0.08 nm -1 It was confirmed that MWCNT aggregate 1 of Example 1, MWCNT aggregate 2 of Example 2, and MWCNT aggregate 3 of Example 3, which contain MWCNTs having a scattering intensity ratio S3 / S4, which is the ratio to the scattering intensity S4 in On the other hand, it was confirmed that SWCNT aggregate 1 of Comparative Example 1, MWCNT aggregate 4 of Comparative Example 2, and MWCNT aggregate 5 of Comparative Example 3, which contain CNTs that do not satisfy the above-mentioned scattering intensity ratio S1 / S2 of 90 or more, have inferior electrical conductivity compared to the Examples. Also, it was confirmed that SWCNT aggregate 1 of Comparative Example 1, MWCNT aggregate 4 of Comparative Example 2, and MWCNT aggregate 5 of Comparative Example 3, which contain CNTs that do not satisfy the above-mentioned scattering intensity ratio S3 / S4 of 10 or less, have inferior electrical conductivity compared to the Examples. [Table 3]

[0220] From the results of measuring the maximum length of MWCNTs by taking SEM photographs, the results of the evaluation of electrical conductivity shown in Tables 1 and 2, and the results shown in Table 3, it was found that the MWCNTs contained MWCNTs with a maximum length of 1000 μm to 30000 μm (so-called ULMWCNTs), the peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum of the MWCNTs, is more than 0.9 and 15 or less, and the BET specific surface area of ​​the MWCNTs is less than 50 m 2 / g~400m 2 It was revealed that the MWCNT aggregates with a Cr content of 1.001g / g have excellent electrical conductivity. The present invention also includes MWCNTs (so-called specific ULMWCNTs) having a maximum length of more than 1600 μm and not more than 30000 μm, in which the peak intensity ratio G1 / D1, which is the ratio of the peak intensity G1 of the G band to the peak intensity D1 of the D band in the Raman spectrum of the MWCNTs, is 10 or less, and the BET specific surface area of ​​the MWCNTs is 200 m 2 / g~300m 2 It was also revealed that the MWCNT aggregates with a conductivity of 0.1 wt. / g also had excellent electrical conductivity.

Claims

1. A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes, which when dispersed in water at a concentration of 0.004 mass%, have a median diameter of 80 nm or more in a volume-based particle size distribution obtained by centrifugal sedimentation, and when dispersed in water at a concentration of 0.2 mass%, have a rate of change in transmittance measured by centrifugal sedimentation of 0.3% / hour or less.

2. When the sample was dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering was q = 0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q at 0.8 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S1 / S2 of 90 or more, the ratio being a scattering intensity S1 / S2 in the multi-walled carbon nanotube array and a scattering intensity S2 in the multi-walled carbon nanotube array.

3. When the compound was dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering was q = 0.02 nm. -1 Scattering intensity S3 and the magnitude of the scattering vector q at q = 0.08 nm -1 A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being a scattering intensity S3 / S4 in the multi-walled carbon nanotube array and a scattering intensity S4 in the multi-walled carbon nanotube array.

4. When the powder is dispersed in water at a concentration of 0.004% by mass, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more, when the powder is dispersed in water at a concentration of 0.2% by mass, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less, and when the powder is dispersed in water at a concentration of 0.2% by mass, the magnitude q of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is 0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q at 0.8 nm -1 The multi-walled carbon nanotube aggregate includes multi-walled carbon nanotubes having a scattering intensity ratio S1 / S2 of 90 or more, the ratio being a scattering intensity S1 / S2 in the multi-walled carbon nanotube array and a scattering intensity S2 in the multi-walled carbon nanotube array.

5. When the powder is dispersed in water at a concentration of 0.004% by mass, the median diameter in the volume-based particle size distribution obtained by centrifugal sedimentation is 80 nm or more, when the powder is dispersed in water at a concentration of 0.2% by mass, the rate of change in transmittance measured by centrifugal sedimentation is 0.3% / hour or less, and when the powder is dispersed in water at a concentration of 0.2% by mass, the magnitude q of the scattering vector in the scattering profile obtained by small-angle X-ray scattering is 0.02 nm. -1 Scattering intensity S3 and the magnitude of the scattering vector q at q = 0.08 nm -1 A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being a scattering intensity S3 / S4 in the multi-walled carbon nanotube array and a scattering intensity S4 in the multi-walled carbon nanotube array.

6. When the sample was dispersed in water at a concentration of 0.2% by mass, the magnitude of the scattering vector in the scattering profile obtained by small-angle X-ray scattering was q = 0.2 nm. -1 Scattering intensity S1 and scattering vector magnitude q at 0.8 nm -1 the scattering intensity ratio S1 / S2, which is the ratio of the scattering intensity S1 to the scattering intensity S2 at the scattering profile, is 90 or more, and the magnitude q of the scattering vector of the scattering profile is 0.02 nm -1 Scattering intensity S3 and the magnitude of the scattering vector q at q = 0.08 nm -1 A multi-walled carbon nanotube aggregate comprising multi-walled carbon nanotubes having a scattering intensity ratio S3 / S4 of 10 or less, the ratio being a scattering intensity S3 / S4 in the multi-walled carbon nanotube array and a scattering intensity S4 in the multi-walled carbon nanotube array.

7. The multi-walled carbon nanotube aggregate according to any one of claims 1 to 6, wherein the multi-walled carbon nanotubes have a maximum length of 1000 µm to 30000 µm.

8. The aggregate of multi-walled carbon nanotubes according to any one of claims 1 to 6, which is a conductive assistant.

9. A multi-walled carbon nanotube dispersion comprising the aggregate of multi-walled carbon nanotubes according to any one of claims 1 to 6 and a dispersion medium.

10. A conductive material comprising the multi-walled carbon nanotube aggregate according to any one of claims 1 to 6.

11. An electrode comprising an electrode active material and the conductive material of claim 10.

12. A secondary battery comprising the electrode according to claim 11.

13. A planar aggregate comprising the multi-walled carbon nanotube aggregate according to any one of claims 1 to 6.

14. A filter using the planar assembly according to claim 13.

15. An electromagnetic wave shield using the planar assembly according to claim 13.

16. A pellicle for extreme ultraviolet rays using the planar assembly according to claim 13.

Citation Information

Patent Citations

  • Multi-layer carbon nanotube, multi-layer carbon nanotube aggregate, and method for producing multi-layer carbon nanotube

    JP2020180028A